Multilayer film and packaging material obtained using same
By adopting a multi-layer film structure in the packaging material, combining EVOH, adhesive resin, polyethylene resin and ethylene-α-olefin copolymer resin, the problem of insufficient mechanical strength and water vapor barrier properties of the packaging material is solved, and the problem of insufficient mechanical strength and water vapor barrier properties of the packaging material is achieved. High mechanical strength and excellent water vapor barrier properties.
Patent Information
- Application Number
- CN202380049227.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-24
- Filing Date
- 2023-06-23
- Publication Date
- 2025-02-11
AI Technical Summary
Existing packaging materials have shortcomings in terms of mechanical strength and water vapor barrier properties, especially in heavy packaging materials, which have insufficient mechanical strength and poor water vapor barrier properties.
A multi-layer film structure is adopted, including ethylene-vinyl alcohol copolymer (EVOH) as the barrier layer, an adhesive resin as the adhesive layer, a polyethylene-based resin as the thermoplastic resin layer, and an ethylene-α-olefin copolymer resin as the hot melt bonding The layer can improve mechanical strength and water vapor barrier properties by optimizing the composition and structure of the layer.
It achieves high mechanical strength and excellent water vapor barrier properties, while maintaining good reuseability, and is suitable for heavy packaging materials.
Smart Images

Figure BDA0005203653830000381 
Figure BDA0005203653830000391 
Figure BDA0005203653830000401
Abstract
Description
Technical Field
[0001] The present invention relates to a multilayer film and a multilayer structure having excellent barrier properties, mechanical properties and recyclability, and a packaging material, a recycling composition and a recycling method obtained using the same. Background Art
[0002] For packaging materials used for long-term storage of food, gas barrier properties, mainly oxygen barrier properties, are mostly required. By using packaging materials with high gas barrier properties, it is possible to suppress the oxidative degradation of food and the reproduction of microorganisms caused by oxygen intrusion. As layers that improve the gas barrier properties, metal foils such as aluminum, inorganic vapor deposition layers such as silicon oxide and aluminum oxide are widely used. On the other hand, resin layers with gas barrier properties such as vinyl alcohol polymers and polyvinylidene chloride are also widely used. Vinyl alcohol polymers have the characteristics of achieving crystallization and high density through hydrogen bonding of hydroxyl groups in the molecules, thereby exerting gas barrier properties. Among them, ethylene-vinyl alcohol copolymer (hereinafter sometimes abbreviated as "EVOH") is suitable for melt molding due to its excellent thermal stability. With the development of co-extrusion technology, multilayer films having an EVOH layer in the middle layer are widely used as gas barrier packaging materials.
[0003] In recent years, the demand for so-called post-consumer recycling (hereinafter sometimes referred to as recycling), which is to recycle and reuse packaging materials consumed by the market, has been increasing worldwide due to environmental and waste issues. The following process is usually used in recycling: the recycled packaging materials are cut, classified and cleaned as needed, and then melt-mixed using an extruder. In this regard, it is required that the packaging materials be composed of a single material as much as possible (monomaterialization), so that high-purity and high-quality recycled raw materials can be obtained.
[0004] Patent document 1 records that although the multilayer film does not have a polyamide layer, it still has excellent mechanical strength and thermoformability. When the recycled material is melt-molded, the generation of pitting caused by resin deterioration (gelation) can be suppressed, and the recyclability is also excellent. The multilayer film has a hard layer with a puncture strength of not less than 40 N / mm and not more than 150 N / mm, and has (1) a resin composition layer having EVOH with a melting point of not less than 170°C and EVOH with a melting point of less than 170°C or (2) a resin composition layer having a modified EVOH containing a modified group having a specific primary hydroxyl group.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2020 / 071513 Summary of the invention
[0008] Problems to be solved by the invention
[0009] However, when used as a packaging material for a heavy content, there is a tendency to require higher mechanical strength, and the multilayer film described in Patent Document 1 sometimes has insufficient mechanical strength. In addition, although the mechanical strength can be improved by increasing the thickness of the multilayer film, the amount of resin used in the packaging material will increase, so it is sought to suppress the thickness as much as possible and effectively improve the mechanical strength. In addition, when the barrier film is used as a packaging material for foods such as soups or liquids such as lotions, or as a packaging material for substances such as powders that solidify when they absorb moisture, it is necessary to suppress the permeation of moisture in order to ensure quality, but the multilayer film described in Patent Document 1 sometimes has insufficient water vapor barrier properties.
[0010] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a multilayer film and a multilayer structure having excellent barrier properties (oxygen barrier properties and water vapor barrier properties), mechanical properties and recyclability, and a packaging material obtained using the same.
[0011] Means used to solve problems
[0012] According to the present invention, the above object is achieved by providing the following technical solutions.
[0013] [1] A multilayer film comprising: a barrier layer (A) comprising an ethylene-vinyl alcohol copolymer (a) having an ethylene unit content of 20 to 50 mol % and a saponification degree of 90 mol % or more (hereinafter sometimes abbreviated as "EVOH (a)") as a main component, an adhesive layer (B) comprising an adhesive resin (b) as a main component, and a film having a density of 0.941 to 0.980 g / cm 3 The thermoplastic resin layer (C) comprises a polyethylene resin (c) as a main component, and a layer having a density of 0.880 to 0.920 g / cm 3 a heat-sealing layer (D) having an ethylene-α-olefin copolymer resin (d) as a main component, a barrier layer (A) between at least one thermoplastic resin layer (C) and the heat-sealing layer (D), and no layer containing a resin having a melting point of 200°C or more as a main component and no metal layer having a thickness of 1 μm or more, wherein when the temperature is increased from -50°C to 220°C at a rate of 10°C / min (first temperature increase) by a differential scanning calorimeter (DSC), then the temperature is decreased to -50°C at a rate of 10°C / min, and then the temperature is increased to 220°C at a rate of 10°C / min (second temperature increase), the ratio (H1 / H2) of the total heat of fusion (H1) at 0 to 150°C during the first temperature increase to the total heat of fusion (H2) at 0 to 150°C during the second temperature increase is 0.75 to 1.01;
[0014] [2] The multilayer film according to [1], wherein the film has a thermoplastic resin layer (C) on one outermost layer and a heat-sealing layer (D) on the other outermost layer;
[0015] [3] The multilayer film according to [1] or [2], wherein an adhesive layer (B1) is provided between the barrier layer (A) and the thermoplastic resin layer (C), and the acid value of the adhesive resin (b1) as a main component of the adhesive layer (B1) is 0.50 mgKOH / g or more and 2.50 mgKOH / g or less;
[0016] [4] The multilayer film according to any one of [1] to [3], wherein the polyethylene resin (c) and the ethylene-α-olefin copolymer resin (d) each have an MFR (at 190°C and 2.16 kg load) measured in accordance with JIS K7210 (2014) of 0.5 to 2.0 g / 10 min;
[0017] [5] The multilayer film according to any one of [1] to [4], wherein the ethylene-α-olefin copolymer resin (d) is a linear low-density polyethylene obtained by copolymerizing ethylene and an α-olefin having 6 or more carbon atoms;
[0018] [6] The multilayer film according to any one of [1] to [5], wherein the heat-sealing layer (D) contains 100 to 7000 ppm of a higher fatty acid amide compound (e) having a melting point of 60 to 120°C;
[0019] [7] The multilayer film according to any one of [1] to [6], wherein the heat-sealed layer (D) contains 500 to 5000 ppm of inorganic oxide particles (f) having an average particle size of 1 to 30 μm, and the inorganic oxide particles (f) are at least one selected from silicon oxide particles and metal oxide particles;
[0020] [8] The multilayer film according to any one of [1] to [7], wherein the barrier layer (A) contains 10 to 200 ppm of at least one polyvalent metal ion (g) selected from magnesium ions, calcium ions and zinc ions;
[0021] [9] The multilayer film according to any one of [1] to [8], wherein the barrier layer (A) contains 10 to 400 ppm of alkali metal ions;
[0022]
[10] The multilayer film according to any one of [1] to [9], wherein the ethylene-vinyl alcohol copolymer (a) comprises EVOH (a1) and EVOH (a2), wherein the EVOH (a1) has an ethylene unit content of 22 mol% or more and less than 34 mol% and a saponification degree of 99 mol% or more, and the EVOH (a2) has an ethylene unit content of 34 mol% or more and less than 50 mol% and a saponification degree of 99 mol% or more;
[0023]
[11] The multilayer film according to any one of [1] to
[10] , wherein when the temperature is increased from -50°C to 220°C at 10°C / min (first temperature increase), then decreased to -50°C at 10°C / min, and then increased to 220°C at 10°C / min (second temperature increase) using a differential scanning calorimeter (DSC), the ratio (H1 / H2) of the total heat of fusion at 150 to 200°C during the first temperature increase to the total heat of fusion at 150 to 200°C during the second temperature increase is 0.90 to 1.35;
[0024]
[12] The multilayer film according to any one of [1] to
[11] , wherein the total thickness of all layers is 200 μm or less, and the ratio of the thickness of the barrier layer (A) to the total thickness of all layers is 0.10 or less;
[0025]
[13] The multilayer film according to any one of [1] to
[12] , wherein the total thickness of all layers is 200 μm or less, and the ratio of the thickness of the thermoplastic resin layer (C) to the total thickness of all layers is 0.20 to 0.60;
[0026]
[14] The multilayer film according to any one of [1] to
[13] , wherein the oxygen permeability at 20°C and 65% RH is 5 cc / (m 2 ·day·atm) or less;
[0027]
[15] The multilayer film according to any one of [1] to
[14] , which has a water vapor transmission rate of 5 g / (m 2 · days) or less;
[0028]
[16] The multilayer film according to any one of [1] to
[15] , wherein after conditioning at 23°C and 50% RH for 24 hours, the elongation at break when punctured at a speed of 50 mm / min with a needle having a tip diameter of 1 mm under the same conditions is 8.0 mm or more;
[0029]
[17] The multilayer film according to any one of [1] to
[16] , wherein after conditioning at 23°C and 50% RH for 24 hours, the breaking strength when punctured at a speed of 50 mm / min with a needle having a tip diameter of 1 mm under the same conditions is 8.5 N or more;
[0030]
[18] The multilayer film according to any one of [1] to
[17] , which has a laminated structure in which a thermoplastic resin layer (C), an adhesive layer (B1), a barrier layer (A), an adhesive layer (B2) and a heat-sealing layer (D) are laminated in this order;
[0031]
[19] A multilayer structure comprising a laminate of the multilayer film according to any one of [1] to
[18] and at least one resin layer (R) containing a thermoplastic resin (h) as a main component;
[0032]
[20] The multilayer structure according to
[19] , wherein the thermoplastic resin (h) contains a polyethylene resin as a main component;
[0033]
[21] A packaging material comprising the multilayer film or multilayer structure according to any one of [1] to
[20] ;
[0034]
[22] A recycling composition comprising a recycled product of the multilayer film or multilayer structure according to any one of [1] to
[20] ;
[0035]
[23] A method for recovering a multilayer film or a multilayer structure, wherein the multilayer film or the multilayer structure according to any one of [1] to
[20] is crushed and then melt-molded.
[0036] Effects of the Invention
[0037] The multilayer film and multilayer structure of the present invention, and a packaging material obtained using the same are excellent in barrier properties, mechanical properties, and recyclability. DETAILED DESCRIPTION
[0038] Hereinafter, embodiments of the present invention will be described. It should be noted that, as materials showing specific functions in the following description, specific materials (compounds, etc.) are sometimes exemplified, but the present invention is not limited to the mode of using such materials. In addition, the exemplified materials can be used alone or in combination as long as there is no special description.
[0039] The multilayer film of the present invention comprises: a barrier layer (A) comprising EVOH (a) having an ethylene unit content of 20 to 50 mol % and a saponification degree of 90 mol % or more as a main component, an adhesive layer (B) comprising an adhesive resin (b) as a main component, and a PVC layer having a density of 0.941 to 0.980 g / cm 3 The thermoplastic resin layer (C) comprises a polyethylene resin (c) as a main component, and a layer having a density of 0.880 to 0.920 g / cm 3A heat-sealing layer (D) having an ethylene-α-olefin copolymer resin (d) as a main component, a barrier layer (A) between at least one group of thermoplastic resin layers (C) and the heat-sealing layer (D), and no layer containing a resin having a melting point of 200°C or more as a main component and no metal layer having a thickness of 1 μm or more. When the temperature is increased from -50°C to 220°C at a rate of 10°C / min (first temperature increase) using a differential scanning calorimeter (DSC), then the temperature is lowered to -50°C at a rate of 10°C / min, and then the temperature is increased to 220°C at a rate of 10°C / min (second temperature increase), the ratio (H1 / H2) of the total heat of fusion (H1) at 0 to 150°C during the first temperature increase to the total heat of fusion (H2) at 0 to 150°C during the second temperature increase is 0.75 to 1.01. Here, "comprising... as a main component" means comprising more than 50% by mass, preferably comprising more than 70% by mass, more preferably comprising more than 80% by mass, further preferably comprising more than 90% by mass, and may be more than 95% by mass, more than 97% by mass, or more than 99% by mass. The multilayer film of the present invention has a tendency to maintain recyclability and improve gas barrier properties by having a barrier layer (A). In addition, by having an adhesive layer (B), it tends to improve mechanical strength and recyclability. In addition, by making the main component of the thermoplastic resin layer (C) have a density of 0.941 to 0.980 g / cm 3 The polyethylene resin (c) has a tendency to exhibit excellent water vapor barrier properties. In addition, the main component of the heat-sealing layer (D) is a polyethylene resin (c) having a density of 0.880 to 0.920 g / cm 3The ethylene-α-olefin copolymer resin (d) thus tends to exhibit excellent mechanical strength. In addition, by making the multilayer film of the present invention not have a layer containing a resin with a melting point of 200°C or higher as a main component and a metal layer with a thickness of 1 μm or more, good recyclability can be exhibited. "Not having a layer containing a resin with a melting point of 200°C or higher as a main component and a metal layer with a thickness of 1 μm or more" means: not having a layer containing a resin with a melting point of 200°C or higher as a main component and not having a metal layer with a thickness of 1 μm or more. Furthermore, by setting the above-mentioned heat of fusion ratio (H1 / H2) of the multilayer film of the present invention to 0.75 to 1.01, even if the thickness of the multilayer film is thin (for example, 200 μm or less), the mechanical strength can be effectively improved. The multilayer film of the present invention has a structure in which a barrier layer (A) is provided between at least one set of a thermoplastic resin layer (C) and a heat-sealing layer (D), thus tending to have the thermoplastic resin layer (C) and the heat-sealing layer (D) easily cooled and the above-mentioned heat of fusion ratio (H1 / H2) easily adjusted. The recyclability in this specification can be evaluated based on the evaluation of pits and coloring in the melt-molded product of the crushed material of the multilayer film and the melt viscosity stability of the crushed material of the multilayer film. Specifically, it can be evaluated using the method described in the examples. The mechanical strength in this specification can be evaluated based on the puncture fracture strength and elongation, impact strength, and drop resistance evaluation. Specifically, it can be evaluated using the method described in the examples. In this specification, "barrier property" refers to oxygen barrier property and water vapor barrier property, and "gas barrier property" refers to oxygen barrier property.
[0040] <EVOH (a) and barrier layer (A)>
[0041] The multilayer film of the present invention has a barrier layer (A) containing EVOH (a) as a main component. Since EVOH (a) has excellent gas barrier property, a multilayer film having a layer containing EVOH (a) as a main component is preferably used as a packaging material with high content retention. In addition, since EVOH (a) can be easily melt-mixed with a polyethylene-based resin, a packaging material with excellent recyclability can be provided. In addition, the content of EVOH (a) in the barrier layer (A) needs to exceed 50% by mass, preferably 70% by mass or more, more preferably 90% by mass or more, and further preferably 95% by mass or more.
[0042] EVOH (a) is usually obtained by saponifying an ethylene-vinyl acetate copolymer obtained by polymerizing ethylene and vinyl acetate. As the vinyl acetate, vinyl acetate can be cited as a representative, and other fatty acid vinyl esters (such as vinyl formate, vinyl propionate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl benzoate, vinyl pivalate, and vinyl versatate) can also be used.
[0043] The ethylene unit content of EVOH (a) is 20 to 50 mol%. If the ethylene unit content is 20 mol% or more, the melt moldability of EVOH (a) and the crushed product of the multilayer film containing EVOH (a) is improved. The ethylene unit content is preferably 23 mol% or more, more preferably 26 mol% or more, and can be 29 mol% or more. On the other hand, if the ethylene unit content is 50 mol% or less, the gas barrier properties of the multilayer film of the present invention are improved. The ethylene unit content is preferably 46 mol% or less, more preferably 42 mol% or less, and can be 38 mol% or less. In addition, the saponification degree of EVOH (a) is 90 mol% or more. The saponification degree refers to the ratio of the number of vinyl alcohol units in EVOH (a) to the total number of vinyl alcohol units and vinyl ester units. If the saponification degree is 90 mol% or more, the gas barrier properties of the multilayer film of the present invention are improved. The saponification degree is preferably 95 mol% or more, more preferably 99 mol% or more, and further preferably 99.9 mol% or more. The saponification degree can be 100 mol% or less. The ethylene unit content and saponification degree of EVOH (a) are determined by 1 It was determined by H-NMR measurement.
[0044] EVOH (a) may be a mixture of two or more EVOHs having different ethylene unit contents. In this case, the difference in ethylene unit content between the EVOHs having the largest difference in ethylene unit content is preferably 30 mol% or less, more preferably 25 mol% or less, further preferably 20 mol% or less, and may be 3 mol% or more. Similarly, EVOH (a) may be a mixture of two or more EVOHs having different degrees of saponification. In this case, the difference in saponification degree between the EVOHs having the largest difference is preferably 7 mol% or less, more preferably 5 mol% or less, and may be 0.5 mol% or more. In the case where it is desired to take into account both thermoformability and gas barrier properties at a higher level, it is preferred that EVOH (a1) having an ethylene unit content of 22 mol% or more and less than 34 mol% and a saponification degree of 99 mol% or more and EVOH (a2) having an ethylene unit content of 34 mol% or more and less than 50 mol% and a saponification degree of 99 mol% or more be mixed in a mixing mass ratio (a1 / a2) of 60 / 40 to 90 / 10, and used as EVOH (a).
[0045] EVOH (a) may contain other monomer units other than ethylene, vinyl ester and vinyl alcohol as long as the effect of the present invention is not impeded. In particular, by introducing a modified group containing a primary hydroxyl group having a specific structure, it is sometimes possible to achieve both high gas barrier properties and molding processability of EVOH (a). The content of other monomer units is preferably 10 mol% or less, more preferably 5 mol% or less, further preferably 1 mol% or less, and particularly preferably substantially free of them. Examples of such other monomers include olefins such as propylene, butene, pentene, and hexene; 3-acyloxy-1-propylene, 3-acyloxy-1-butene, 4-acyloxy-1-butene, 3,4-diacyloxy-1-butene, 3-acyloxy-4-methyl-1-butene, 4-acyloxy-1-butene, 3,4-diacyloxy-1-butene, 3-acyloxy-4-methyl-1-butene, 4-acyloxy-2-methyl-1-butene, 4-acyloxy-3-methyl-1-butene, 3,4-diacyloxy-2-methyl-1-butene, 4-acyloxy-1-pentene, 5-acyloxy-1-pentene, 4,5-diacyloxy-1-pentene, 4-acyloxy-1-hexene, 5-acyloxy-1-hexene, 6-acyloxy-1-pentene, 6 ...1-pentene, 6-acyloxy-1-pentene, 6-acyloxy-1-pentene, 6-acyloxy-1-pentene, 6-acyloxy-1-pentene, 6-acyloxy-1-pentene, 6-acyloxy-1-pentene, 6-acyloxy-1-pentene, 6-acyloxy-1-pentene, 6-acyloxy-1-pentene Olefins containing ester groups, such as 1-hexene, 5,6-diacyloxy-1-hexene, and 1,3-diacetoxy-2-methylenepropane, or saponified products thereof; unsaturated acids, such as acrylic acid, methacrylic acid, crotonic acid, and itaconic acid, or anhydrides, salts, or monoalkyl esters or dialkyl esters thereof; nitriles, such as acrylonitrile and methacrylonitrile; amides, such as acrylamide and methacrylamide; olefin sulfonic acids, such as vinyl sulfonic acid, allyl sulfonic acid, and methyl allyl sulfonic acid, or salts thereof; vinyl silane compounds, such as vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tri(β-methoxy-ethoxy)silane, and γ-methacryloxypropylmethoxysilane; alkyl vinyl ethers, vinyl ketone, N-vinyl pyrrolidone, vinyl chloride, and vinylidene chloride.
[0046] EVOH (a) can be modified by urethanization, acetalization, cyanoethylation, oxyalkyleneization, etc. as required. Oxyalkyleneization can be carried out using epoxy compounds, such as ethylene oxide (ethylene oxide), propylene oxide, 1,2-butylene oxide, 2,3-butylene oxide, 3-methyl-1,2-butylene oxide, 1,2-pentylene oxide, 3-methyl-1,2-pentylene oxide, 1,2-epoxyhexane, 2,3-epoxyhexane, 3,4-epoxyhexane, 3-methyl-1,2-epoxyhexane, 3-methyl-1,2-epoxyheptane, 4-methyl-1, 2-Epoxyheptane, 1,2-epoxyoctane, 2,3-epoxyoctane, 1,2-epoxynonane, 2,3-epoxynonane, 1,2-epoxydecane, 1,2-epoxydodecane, ethylene oxide benzene, 1-phenyl-1,2-propane, 3-phenyl-1,2-epoxypropylene, various alkyl glycidyl ethers, various alkylene glycol monoglycidyl ethers, various alkenyl glycidyl ethers, various oxirane alcohols such as glycidol, various cycloalkylene oxides, various cycloalkylene oxides, etc. Among them, 1,2-butylene oxide, 2,3-butylene oxide, propylene oxide, ethylene oxide or glycidol is preferred, and propylene oxide or glycidol is more preferred.
[0047] The MFR (190°C, 2.16 kg load) of EVOH (a) measured in accordance with JIS K7210 (2014) is preferably 0.2 to 20 g / 10 min. The MFR of EVOH (a) is more preferably 0.5 g / 10 min or more, and further preferably 0.8 g / 10 min or more. On the other hand, the MFR of EVOH (a) is more preferably 15 g / 10 min or less, further preferably 10 g / 10 min or less, further preferably 5 g / 10 min or less, and particularly preferably 3 g / 10 min or less. If the MFR of EVOH (a) is within the above range, the melt-formability of the crushed product of EVOH (a) and the multilayer film containing EVOH (a) (the multilayer film of the present invention) is improved.
[0048] <Polyvalent Metal Ions (g)>
[0049] The barrier layer (A) preferably contains 10 to 200 ppm of at least one polyvalent metal ion (g) selected from magnesium ions, calcium ions and zinc ions. By containing a predetermined amount of polyvalent metal ions (g), thickening, gelation and adhesion of resin to the screw when the crushed product of EVOH (a) and the multilayer film containing EVOH (a) are melt-molded are suppressed. In the barrier layer (A), as the polyvalent metal ion (g), it is more preferred to contain magnesium ions or calcium ions, and it is further preferred to contain magnesium ions. In addition, it is preferred to contain the polyvalent metal ion (g) in the form of a carboxylate. As the carboxylic acid at this time, any of aliphatic carboxylic acids and aromatic carboxylic acids can be used, and aliphatic carboxylic acids are preferred. As aliphatic carboxylic acids, for example, formic acid, acetic acid, propionic acid, butyric acid, lauric acid, stearic acid, myristic acid, behenic acid, montanic acid, etc. can be listed, and higher fatty acids with 10 to 25 carbon atoms are more preferred. In addition, from the viewpoint of suppressing coloration during melt molding, the polyvalent metal ion (g) is also preferably contained in the form of a salt of the polyvalent carboxylic acid described later.
[0050] The content of the polyvalent metal ion (g) in the barrier layer (A) is preferably 10 to 200 ppm in terms of metal atom conversion. If the content is 10 ppm or more, the viscosity stability of the crushed material of EVOH (a) and the multilayer film containing EVOH (a) becomes good, and the gelation of the resin and the adhesion of the resin to the extruder screw are suppressed. The lower limit of the content of the polyvalent metal ion (g) is more preferably 20 ppm. On the other hand, if the content of the polyvalent metal ion (g) is less than 200 ppm, the excessive decomposition of the crushed material of the multilayer film containing EVOH (a) is suppressed, and the hue of the recovered composition becomes good. The upper limit of the content of the polyvalent metal ion (g) is more preferably 160 ppm, and further preferably 120 ppm.
[0051] The barrier layer (A) may contain other components in addition to EVOH (a) and the polyvalent metal ion (g) as long as it does not hinder the effect of the present invention. As other components, for example, alkali metal ions, polyvalent metal ions other than the polyvalent metal ion (g), carboxylic acids, phosphoric acid compounds, boron compounds, oxidation promoters, antioxidants, plasticizers, heat stabilizers (melt stabilizers), photoinitiators, deodorants, ultraviolet absorbers, antistatic agents, lubricants, colorants, fillers, desiccants, fillers, pigments, dyes, processing aids, flame retardants and antifogging agents can be listed. In particular, from the viewpoint of improving the interlayer adhesion and melt moldability of the laminate containing EVOH (a), it is preferred to contain alkali metal ions. In addition, from the viewpoint of being able to suppress coloring when EVOH (a) and the recycled resin containing EVOH (a) are melt-molded, it is preferred to contain carboxylic acids and / or phosphoric acid compounds. Furthermore, by including a boron compound, the melt viscosity of EVOH (a) and the recycled resin including EVOH (a) can be controlled, and the mechanical strength of the multilayer film of the present invention can be improved. The content of other components in the barrier layer (A) is usually 5% by mass or less, preferably 3% by mass or less, and more preferably 1% by mass or less.
[0052] <Alkali metal ions>
[0053] The barrier layer (A) preferably contains 10 to 400 ppm of alkali metal ions. The lower limit of the alkali metal ion content is more preferably 100 ppm, and further preferably 150 ppm. On the other hand, the upper limit of the alkali metal ion content is more preferably 350 ppm, and can be 250 ppm. If the content of alkali metal ions is 10 ppm or more, the interlayer adhesion in the multilayer film of the present invention comprising a layer obtained by molding EVOH (a) becomes good. On the other hand, if the content of alkali metal ions is 400 ppm or less, there is a tendency to suppress coloring. In addition, by controlling the content ratio of alkali metal ions to the carboxylic acid described later, the melt moldability and coloring resistance can be further improved.
[0054] As alkali metal ions, for example, ions of lithium, sodium, potassium, rubidium, and cesium can be cited, and from the viewpoint of industrial acquisition, ions of sodium or potassium are preferred. In particular, by using sodium ions, it is sometimes possible to take into account both the hue and the interlayer adhesion with the adhesive layer (B) at a high level. They can be used alone or in combination of two or more.
[0055] Examples of alkali metal salts that provide alkali metal ions include aliphatic carboxylates, aromatic carboxylates, carbonates, hydrochlorides, nitrates, sulfates, phosphates, and metal complexes of alkali metals such as sodium and potassium. Among them, from the viewpoint of easy availability, at least one selected from sodium acetate, potassium acetate, sodium phosphate, and potassium phosphate is more preferred.
[0056] <Carboxylic acid>
[0057] The barrier layer (A) preferably contains carboxylic acid. The lower limit of the carboxylic acid content is preferably 50 ppm, more preferably 100 ppm. On the other hand, the upper limit of the carboxylic acid content is preferably 400 ppm, more preferably 350 ppm. If the carboxylic acid content is within the above range, there is a tendency to suppress hue deterioration. The carboxylic acid content can be determined by extracting 10 g of the resin composition constituting the barrier layer (A) with 50 ml of pure water at 95°C for 8 hours and then titrating the resulting extract. It should be noted that, as the carboxylic acid content in the resin composition, carboxylic acids present in the form of salts in the aforementioned extract are not considered. In addition, in the case where the resin composition contains acidic compounds other than carboxylic acids, the carboxylic acid content in the resin composition can be determined by subtracting the contribution of these acidic compounds from the measured value based on titration.
[0058] The pKa of the carboxylic acid is preferably 3.5 to 5.5. When the pKa of the carboxylic acid is within the above range, the pH buffering capacity in the weakly acidic range is improved, the melt moldability is further improved, and the coloring effect caused by acidic substances and basic substances can be further reduced.
[0059] The carboxylic acid may be a monocarboxylic acid. One of them may be used alone or two or more of them may be used in combination. A monocarboxylic acid refers to a compound having one carboxyl group in the molecule. There are no particular limitations on monocarboxylic acids having a pKa in the range of 3.5 to 5.5, and examples thereof include formic acid (pKa = 3.77), acetic acid (pKa = 4.76), propionic acid (pKa = 4.85), acrylic acid (pKa = 4.25), and the like. These carboxylic acids may further have substituents such as hydroxyl groups, amino groups, and halogen atoms. Among them, acetic acid is preferred from the perspective of high safety, easy acquisition, and handling.
[0060] The carboxylic acid may be a polycarboxylic acid. If the carboxylic acid is a polycarboxylic acid, the coloring resistance of EVOH (a) at high temperatures and the coloring resistance of a melt-molded product of a multilayer film containing EVOH (a) can sometimes be further improved. In addition, the polycarboxylic acid compound also preferably has more than 3 carboxyl groups. In this case, the coloring resistance can sometimes be more effectively improved. Polycarboxylic acid refers to a compound having more than 2 carboxyl groups in the molecule. In this case, it is preferred that the pKa of at least one carboxyl group is in the range of 3.5 to 5.5, and examples thereof include oxalic acid (pKa2=4.27), succinic acid (pKa1=4.20), fumaric acid (pKa2=4.44), malic acid (pKa2=5.13), glutaric acid (pKa1=4.30, pKa2=5.40), adipic acid (pKa1=4.43, pKa2=5.41), pimelic acid (pKa1=4.71), phthalic acid (pKa2=5.41), isophthalic acid (pKa2=4.46), terephthalic acid (pKa1=3.51, pKa2=4.82), citric acid (pKa2=4.75), tartaric acid (pKa2=4.40), glutamic acid (pKa2=4.07), and aspartic acid (pKa=3.90).
[0061] <Phosphoric acid compounds>
[0062] The barrier layer (A) may further contain a phosphate compound. The lower limit of the content of the phosphate compound is preferably 5 ppm in terms of phosphate radical conversion. On the other hand, the upper limit of the content of the phosphate compound is preferably 100 ppm in terms of phosphate radical conversion. By containing the phosphate compound within this range, the coloring of the melt-molded product of the crushed product of the EVOH (a) and the multilayer film is sometimes suppressed, thereby improving thermal stability.
[0063] As the phosphoric acid compound, various acids such as phosphoric acid and phosphorous acid, and salts thereof can be used. The phosphate can be any of dihydrogen phosphate, monohydrogen phosphate, and phosphate. The cationic species of the phosphate is also not particularly limited, and the cationic species is preferably an alkali metal or an alkaline earth metal. Among them, as the phosphoric acid compound, sodium dihydrogen phosphate, potassium dihydrogen phosphate, disodium hydrogen phosphate, and dipotassium hydrogen phosphate are preferred.
[0064] <Boron compounds>
[0065] The barrier layer (A) may further contain a boron compound. The lower limit of the content of the boron compound is preferably 50 ppm, more preferably 100 ppm, in terms of boron element conversion. On the other hand, the upper limit of the content of the boron compound is preferably 400 ppm, more preferably 200 ppm, in terms of boron element conversion. By containing the boron compound within this range, the thermal stability of the crushed product of EVOH (a) and the multilayer film during melt molding is sometimes improved, and the generation of gel and pitting is suppressed. In addition, the pull-down resistance and the necking resistance during film making are sometimes improved, and the mechanical properties of the multilayer film are sometimes improved. It can be inferred that these effects are caused by the chelating interaction between EVOH (a) and the boron compound.
[0066] Examples of the boron compound include boric acid, boric acid esters, borate salts, and boron hydride. Specifically, examples include boric acids such as orthoboric acid (H3BO3), metaboric acid, and tetraboric acid; boric acid esters such as trimethyl borate and triethyl borate; and alkali metal salts or alkaline earth metal salts of the above-mentioned boric acids, borate salts such as borax, and the like. Among them, orthoboric acid is preferred.
[0067] <Hindered Phenol Compounds>
[0068] The barrier layer (A) may further contain, as an antioxidant, a hindered phenolic compound having, for example, an ester bond or an amide bond. The content of the hindered phenolic compound is preferably 1000 to 10000 ppm. If the content is 1000 ppm or more, the coloring, viscosity increase and gelation of the resin can be suppressed when the crushed product of the multilayer film is melt-molded. The content of the hindered phenolic compound is more preferably 2000 ppm or more. On the other hand, if the content of the hindered phenolic compound is less than 10000 ppm, the coloring and bleeding from the hindered phenolic compound can be suppressed. The content of the hindered phenolic compound is more preferably 8000 ppm or less.
[0069] The hindered phenol compound has at least one hindered phenol group. The hindered phenol group refers to a group in which a bulky substituent is bonded to at least one carbon adjacent to the carbon to which the hydroxyl group is bonded in phenol. The bulky substituent is preferably an alkyl group having 1 to 10 carbon atoms, and more preferably a tert-butyl group.
[0070] The hindered phenol compound is preferably in a solid state near room temperature. From the viewpoint of inhibiting the oozing out of the compound, the melting point or softening temperature of the hindered phenol compound is preferably above 50°C, more preferably above 60°C, and further preferably above 70°C. In addition, from the viewpoint of inhibiting the oozing out, the molecular weight of the hindered phenol compound is preferably above 200, more preferably above 400, and further preferably above 600. On the other hand, the molecular weight is usually below 2000. In addition, from the viewpoint of easy mixing with EVOH (a), the melting point or softening temperature of the hindered phenol compound is preferably below 200°C, more preferably below 190°C, and further preferably below 180°C.
[0071] The hindered phenol compound has an ester bond or an amide bond. Examples of the hindered phenol compound having an ester bond include esters of aliphatic carboxylic acids having a hindered phenol group and aliphatic alcohols, and examples of the hindered phenol compound having an amide bond include amides of aliphatic carboxylic acids having a hindered phenol group and aliphatic amines. Among them, the hindered phenol compound preferably has an amide bond from the viewpoint of being easily mixed with EVOH (a).
[0072] Specific structures of hindered phenol compounds include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] sold as Irganox 1010 by BASF, stearyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate sold as Irganox 1076, 2,2'-dithiodiethyl bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] sold as Irganox 1035, and 1,2-di-thiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] sold as Irganox 1040. 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid octadecyl ester sold as Irganox 1135, bis(ethylene oxide)bis(3-tert-butyl-4-hydroxy-5-methylphenylpropionate) sold as Irganox 245, 1,6-hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] sold as Irganox 259, and N,N'-hexamethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide] sold as Irganox 1098. Among them, N,N′-hexamethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide] sold as Irganox 1098 and pentaerythritoltetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] sold as Irganox 1010 are preferred, and Irganox 1098 is more preferred.
[0073] The barrier layer (A) may further contain a thermoplastic resin other than EVOH (a). Examples of the thermoplastic resin other than EVOH (a) include various polyolefins (polyethylene, polypropylene, poly-1-butene, poly-4-methyl-1-pentene, ethylene-propylene copolymers, copolymers of ethylene and α-olefins having 4 or more carbon atoms, copolymers of polyolefins and maleic anhydride, ethylene-vinyl ester copolymers, ethylene-acrylate copolymers, or modified polyolefins obtained by grafting these with unsaturated carboxylic acids or derivatives thereof), various polyamides (nylon 6, nylon 6.6, nylon 6 / 66 copolymers, nylon 11, nylon 12, poly(m-xylylene adipamide), various polyesters (polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate), polyvinyl chloride, polyvinylidene chloride, polystyrene, polyacrylonitrile, polyurethane, polycarbonate, polyacetal, polyacrylate, and modified polyvinyl alcohol resins. The content of the thermoplastic resin in the barrier layer (A) is less than 50% by mass, preferably 30% by mass or less, more preferably 10% by mass or less, further preferably 5% by mass or less, and may be 1% by mass or less.
[0074] As the resin constituting the barrier layer (A), the proportion of EVOH (a) is preferably 60% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, and may be 95% by mass or more, 97% by mass or more, or 99% by mass or more. The resin constituting the barrier layer (A) may consist of EVOH (a) alone. In addition, the proportion of EVOH (a) in the barrier layer (A) is preferably 60% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, and may be 95% by mass or more, 97% by mass or more, or 99% by mass or more. The barrier layer (A) may consist essentially of EVOH (a) alone.
[0075] In the case where the barrier layer (A) contains components other than EVOH (a), the method for producing the resin composition constituting the barrier layer (A) is not particularly limited, and it can be produced by melt-kneading EVOH (a) and other additives (polyvalent metal ions (g), etc.) as required. Other additives can be blended in a solid state such as powder or in the form of a melt, or can be blended as a solute contained in a solution or a dispersoid contained in a dispersion. As solutions and dispersions, aqueous solutions and aqueous dispersions are suitable, respectively. For melt kneading, known mixing devices or mixing devices such as kneading extruders, extruders, open rolls, Banbury mixers, etc. can be used. The temperature range during melt kneading can be appropriately adjusted according to the melting point of the EVOH (a) used, etc., and is generally 150 to 300°C.
[0076] In another embodiment, a masterbatch containing other additives at a high concentration in EVOH (a) can be produced by melt kneading, and the masterbatch can be dry-mixed with EVOH (a) that does not substantially contain other additives to produce a multilayer film. In another embodiment, EVOH (a) and other additives can be used to produce a multilayer film by dry mixing. Dry mixing refers to mechanical mixing in the form of powder or pellets. Mixing can be carried out using a mixing device such as a rotary drum, a ribbon agitator, or a Henschel mixer, or by manual stirring, shaking, etc. in a closed container. The mixing temperature can be room temperature to below the melting point of EVOH (a), and mixing can be carried out in an air atmosphere or a nitrogen atmosphere.
[0077] <Adhesive Resin (b) and Adhesive Layer (B)>
[0078] The multilayer film of the present invention has an adhesive layer (B) containing an adhesive resin (b) as a main component. The adhesive layer (B) has the function of bonding the barrier layer (A) to the thermoplastic resin layer (C) or bonding the barrier layer (A) to the hot melt layer (D). Therefore, the adhesive layer (B) is preferably present between the barrier layer (A) and the thermoplastic resin layer (C) or between the barrier layer (A) and the hot melt layer (D), and is preferably directly stacked with the barrier layer (A) and the thermoplastic resin layer (C) or directly stacked with the barrier layer (A) and the hot melt layer (D). The adhesive layer (B) between the barrier layer (A) and the thermoplastic resin layer (C) is set as an adhesive layer (B1), and the resin constituting the adhesive layer (B1) is set as an adhesive resin (b1). In addition, the adhesive layer (B) between the barrier layer (A) and the heat-sealing layer (D) is referred to as the adhesive layer (B2), and the resin constituting the adhesive layer (B2) is referred to as the adhesive resin (b2). The adhesive resin (b1) and the adhesive resin (b2) may be the same or different. The content of the adhesive resin (b) in the adhesive layer (B) must be more than 50% by mass, preferably 70% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more.
[0079] As the adhesive resin (b), for example, a modified olefin polymer containing a carboxyl group obtained by chemically bonding an unsaturated carboxylic acid or its anhydride to an olefin polymer by an addition reaction, a grafting reaction, etc. can be cited. As the unsaturated carboxylic acid or its anhydride, maleic acid, maleic anhydride, fumaric acid, acrylic acid, methacrylic acid, crotonic acid, itaconic acid, citraconic acid, hexahydrophthalic anhydride, etc. can be cited, among which maleic anhydride is preferably used. Specifically, as a suitable material, one or a mixture of two or more selected from maleic anhydride grafted modified polyethylene, maleic anhydride grafted modified polypropylene, maleic anhydride grafted modified ethylene-propylene copolymer, maleic anhydride grafted modified ethylene-ethyl acrylate copolymer, maleic anhydride grafted modified ethylene-vinyl acetate copolymer, etc. can be cited, and among these, maleic anhydride grafted modified polyethylene is most preferably used. The acid value of this adhesive resin (b) is usually 0.5 to 5 mgKOH / g, preferably 1 to 4 mgKOH / g. In addition, when the adhesive resin (b) is an adhesive resin (b1), the acid value of the adhesive resin (b1) is preferably 0.50 mgKOH / g or more and 2.50 mgKOH / g or less. If the acid value of the adhesive resin (b1) is within the above range, the appearance characteristics and adhesion of the obtained multilayer film can be taken into account at a high level. The acid value of the adhesive resin (b) can be measured using xylene as a solvent in accordance with JIS K 0070:1992.
[0080] The adhesive resin (b) of the present invention may be a mixture of an unmodified resin (bx) and an acid-modified resin (by). In this case, from the viewpoint of further improving the mechanical strength, the unmodified resin (bx) preferably contains the ethylene-α-olefin copolymer resin (d) described later, and more preferably the ethylene-α-olefin copolymer resin (d). Here, when the unmodified resin (bx) contains the ethylene-α-olefin copolymer resin (d), the ethylene-α-olefin copolymer resin (d) contained in the adhesive layer (B) and the ethylene-α-olefin copolymer resin (d) contained in the heat-sealing layer (D) may be the same or different, but are preferably the same. In addition, the ratio (bx / by) of the unmodified resin (bx) to the acid-modified resin (by) in the adhesive resin (b) is preferably 55 / 45 to 95 / 5, and preferably 65 / 35 to 90 / 10. In this case, as the acid-modified resin (by), a resin with a higher degree of acid modification can be preferably used, and its acid value is preferably 5 to 30 mgKOH / g, and more preferably 8 to 20 mgKOH / g. As a result, it is sometimes possible to maintain the necessary interlayer bonding strength and further improve the mechanical strength of the obtained multilayer film. When the adhesive resin (b) of the present invention is a mixture of an unmodified resin (bx) and an acid-modified resin (by), a substance obtained by pre-melting the unmodified resin (bx) and the acid-modified resin (by) can be used, or a substance obtained by dry-mixing the unmodified resin (bx) and the acid-modified resin (by) can be used. For melt mixing, known mixing devices or mixing devices such as a kneading extruder, an extruder, an open roll, and a Banbury mixer can be used. The temperature range during melt mixing can be appropriately adjusted according to the melting points of the unmodified resin (bx) and the acid-modified resin (by) used, and is generally 150 to 300°C. Dry mixing refers to mechanical mixing in the form of powder or pellets. Mixing can be performed using a mixing device such as a drum, a ribbon stirrer, or a Henschel mixer, or can be performed by manually stirring or shaking in a closed container. The mixing temperature can be room temperature to a temperature lower than the melting point of the unmodified resin (bx) and the acid-modified resin (by), and the mixing can be performed in an air atmosphere or a nitrogen atmosphere.
[0081] The adhesive layer (B) may contain other ingredients in addition to the adhesive resin (b) as long as it does not hinder the effect of the present invention. As other ingredients, for example, alkali metal ions, polyvalent metal ions, carboxylic acids, phosphoric acid compounds, boron compounds, oxidation promoters, antioxidants, plasticizers, heat stabilizers (melt stabilizers), photoinitiators, deodorants, ultraviolet absorbers, antistatic agents, lubricants, colorants, fillers, desiccants, fillers, pigments, dyes, processing aids, flame retardants and antifogging agents can be listed. The content of other ingredients in the adhesive layer (B) is usually 5% by mass or less, preferably 3% by mass or less, and more preferably 1% by mass or less. In addition, the adhesive layer (B) may also contain a thermoplastic resin in addition to the adhesive resin (b). As the thermoplastic resin, the above-mentioned resins exemplified as thermoplastic resins that can be included in the barrier layer (A) can be used. The content of the thermoplastic resin in the adhesive layer (B) is less than 50% by mass, preferably less than 30% by mass, more preferably less than 10% by mass, further preferably 5% by mass or less, and may be 1% by mass or less.
[0082] As the resin constituting the adhesive layer (B), the proportion of the adhesive resin (b) is preferably 60% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, and can be 95% by mass or more, 97% by mass or more, or 99% by mass or more. The resin constituting the adhesive layer (B) may consist of only the adhesive resin (b). In addition, the proportion of the adhesive resin (b) in the adhesive layer (B) is preferably 60% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, and can be 95% by mass or more, 97% by mass or more, or 99% by mass or more. The adhesive layer (B) may consist essentially of only the adhesive resin (b).
[0083] <Polyethylene Resin (c) and Thermoplastic Resin Layer (C)>
[0084] The multilayer film of the present invention has a density of 0.941 to 0.980 g / cm 3 The thermoplastic resin layer (C) is a thermoplastic resin layer (C) having a polyethylene resin (c) as a main component. The thermoplastic resin layer (C) has the function of reducing the water vapor transmission rate of the obtained multilayer film. The content of the polyethylene resin (c) in the thermoplastic resin layer (C) must be more than 50% by mass, preferably more than 70% by mass, more preferably more than 90% by mass, and further preferably more than 95% by mass.
[0085] The density of the polyethylene resin (c) is 0.941 to 0.980 g / cm 3 If the density is within the above range, the water vapor barrier property of the obtained multilayer film is improved. The lower limit of the density is preferably 0.945 g / cm 3 , more preferably 0.950 g / cm3 , more preferably 0.955 g / cm 3 The upper limit of density is preferably 0.975 g / cm 3 , more preferably 0.970 g / cm 3 , more preferably 0.965 g / cm 3 .
[0086] The MFR (190°C, 2.16 kg load) of the polyethylene resin (c) is preferably 0.5 to 2.0 g / 10 minutes. If the MFR is within the above range, the polyethylene resin (c) has excellent melt processability, and the various mechanical strengths such as puncture elongation and tensile elongation of the obtained multilayer film are improved. The lower limit of MFR is preferably 0.7 g / 10 minutes. The upper limit of MFR is preferably 1.5 g / 10 minutes, and more preferably 1.1 g / 10 minutes. MFR is measured in accordance with JIS K 7210 (2014) at 190°C and 2.16 kg load.
[0087] Examples of the polyethylene resin (c) include polyethylene resins obtained by polymerizing ethylene and resins obtained by polymerizing ethylene and α-olefins having 3 or more carbon atoms. Examples of α-olefins having 3 or more carbon atoms include propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, and 4-methyl-1-pentene. Among these, polyethylene resins are preferred from the viewpoint of water vapor barrier properties, and high-density polyethylene (HDPE) is more preferred.
[0088] As the polyethylene resin (c), commercially available products may be used, and examples thereof include "NOVATEC (trademark) HD" (manufactured by Nippon Polyethylene Co., Ltd.), "HI-ZEX (trademark)" (manufactured by Prime Polymer Co., Ltd.), and "EVOLUE (trademark) H" (manufactured by Prime Polymer Co., Ltd.).
[0089] <Ethylene-α-olefin copolymer resin (d) and heat-sealing layer (D)>
[0090] The multilayer film of the present invention has a density of 0.880 to 0.920 g / cm 3 The heat-sealing layer (D) is mainly composed of an ethylene-α-olefin copolymer resin (d). The heat-sealing layer (D) has a function as a sealing layer when forming a packaging material, and on this basis, it also has a function of improving various mechanical strengths such as puncture elongation and tensile elongation. The content of the ethylene-α-olefin copolymer resin (d) in the heat-sealing layer (D) must be more than 50% by mass, preferably more than 70% by mass, more preferably more than 90% by mass, and further preferably more than 95% by mass.
[0091] The density of the ethylene-α-olefin copolymer resin (d) is 0.880 to 0.920 g / cm 3 When the density is within the above range, the obtained multilayer film is soft and easy to handle, and various mechanical strengths such as puncture elongation and tensile elongation are improved. The lower limit of the density is preferably 0.885 g / cm 3 , more preferably 0.890 g / cm 3 , more preferably 0.895 g / cm 3 The upper limit of density is preferably 0.915 g / cm 3 , more preferably 0.910 g / cm 3 , more preferably 0.905 g / cm 3 .
[0092] The MFR (190°C, 2.16 kg load) of the ethylene-α-olefin copolymer resin (d) is preferably 0.5 to 2.0 g / 10 minutes. If the MFR is within the above range, the melt processability of the ethylene-α-olefin copolymer resin (d) is excellent, and various mechanical strengths such as puncture elongation and tensile elongation of the obtained multilayer film are improved. The lower limit of MFR is preferably 0.7 g / 10 minutes. The upper limit of MFR is preferably 1.5 g / 10 minutes, and more preferably 1.0 g / 10 minutes. MFR is measured in accordance with JIS K 7210 (2014) at 190°C and 2.16 kg load.
[0093] The total heat of fusion in the melting curve when the ethylene-α-olefin copolymer resin (d) is heated at 10°C / min by a differential scanning calorimeter (DSC) is preferably 150 J / g or less. If the total heat of fusion is within the above range, the melt processability of the ethylene-α-olefin copolymer resin (d) is excellent, and the resulting multilayer film is soft and various mechanical strengths such as puncture elongation and tensile elongation are improved. The total heat of fusion is more preferably 125 J / g or less, further preferably 100 J / g or less, and particularly preferably 90 J / g or less. The lower limit of the total heat of fusion is not particularly limited, and from the viewpoint of the operability and heat resistance of the resulting multilayer film, it is preferably 70 J / g or more, and more preferably 80 J / g or more. The total heat of fusion can be adjusted by the type of α-olefin, the ratio of ethylene to α-olefin, the distribution in the polymer chain, and the degree of polymerization.
[0094] In the melting curve when the temperature of ethylene-α-olefin copolymer resin (d) is raised at 10°C / min by differential scanning calorimeter (DSC), when the melting peak is divided at 100°C, the melting heat of 100°C or more is preferably 60J / g or less. If the melting heat of 100°C or more is in the above range, the ethylene-α-olefin copolymer resin (d) sometimes has both softness and toughness, and various mechanical strengths such as puncture elongation and tensile elongation are improved. The melting heat of 100°C or more is more preferably 50J / g or less, further preferably 40J / g or less, particularly preferably 30J / g or less, and can be 20J / g or less. The lower limit of the melting heat of 100°C or more is not particularly limited, and from the viewpoint of the operability and heat resistance of the obtained multilayer film, it is preferably 5J / g or more, and more preferably 10J / g or more. The melting heat of 100°C or more can be adjusted by the type of α-olefin, the ratio of ethylene to α-olefin, the distribution in the polymer chain, and the degree of polymerization.
[0095] In the melting curve when the temperature of the ethylene-α-olefin copolymer resin (d) is raised at 10°C / min by a differential scanning calorimeter (DSC), when the melting peak is divided at 100°C, the ratio (percentage) of the melting heat below 100°C in the total melting heat is preferably 45% or more. If the ratio of the melting heat below 100°C is within the above range, the obtained multilayer film is soft and various mechanical strengths such as puncture elongation and tensile elongation are improved. The ratio of the melting heat below 100°C is more preferably 60% or more, and further preferably 75% or more. The upper limit of the ratio of the melting heat below 100°C is not particularly limited, and from the viewpoint of the operability and heat resistance of the obtained multilayer film, it is preferably 90% or less, and more preferably 85% or less. The above ratio can be adjusted by the type of α-olefin, the ratio of ethylene to α-olefin, the distribution in the polymer chain, and the degree of polymerization.
[0096] Ethylene-α-olefin copolymer resin (d) is a resin obtained by polymerizing ethylene with an α-olefin having more than 3 carbon atoms. As α-olefins having more than 3 carbon atoms, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 4-methyl-1-pentene, etc. can be listed. Among these, ethylene-α-olefin copolymer resin (d) is preferably a linear low-density polyethylene obtained by polymerizing ethylene with an α-olefin having more than 6 carbon atoms, and more preferably a linear low-density polyethylene obtained by polymerizing ethylene with an α-olefin having more than 8 carbon atoms. In the case where the carbon number of the α-olefin copolymerized with ethylene is large, various mechanical strengths such as puncture elongation and tensile elongation are sometimes significantly improved.
[0097] In addition, as a polymerization catalyst, a metallocene catalyst is preferably used. The linear low-density polyethylene obtained by polymerization using a metallocene catalyst is manufactured by copolymerizing ethylene and α-olefins in the presence of a catalyst formed by a transition metal of the 4th group of the periodic table of elements having at least one ligand with a cyclopentadienyl skeleton, preferably a zirconium compound, an organic aluminum oxide compound, and various components added as needed. The linear low-density polyethylene obtained by polymerization using a metallocene catalyst has excellent melt moldability, and the heat resistance, flexibility, and mechanical strength of the obtained multilayer film are excellent.
[0098] Industrial products of linear low-density polyethylene obtained by polymerizing ethylene and α-olefins having 6 or more carbon atoms using a metallocene catalyst are already on sale, and examples thereof include "EVOLUE (trademark)" (manufactured by Prime Polymer Co., Ltd.), "SUMIKATHENE (trademark)" (manufactured by Sumitomo Chemical Co., Ltd.), "UMERIT (trademark)" (manufactured by UBE-MARUZEN POLYETHYLENE Co., Ltd.), and "ELITE (trademark)" (manufactured by Dow Chemical Co., Ltd.).
[0099] <Higher fatty acid amide compound (e)>
[0100] The heat-sealing layer (D) preferably contains 100 to 7000 ppm of a higher fatty acid amide compound (e) having a melting point of 60 to 120°C. By making the heat-sealing layer (D) contain the higher fatty acid amide compound (e) in the above range, the fluctuation of the mechanical strength measurement value can be reduced regardless of the storage environment and the measurement position, and the stability of the mechanical strength can be improved. In particular, even when the multilayer film is stored at high temperature for a long time, the fluctuation of the mechanical strength can be suppressed, and thus the reliability as a packaging material can be improved.
[0101] The lower limit of the content of the higher fatty acid amide compound (e) in the heat-sealing layer (D) is preferably 100 ppm, more preferably 300 ppm, further preferably 500 ppm, and particularly preferably 700 ppm. The upper limit of the content of the higher fatty acid amide compound (e) is preferably 7000 ppm, more preferably 5000 ppm, further preferably 3000 ppm, particularly preferably 1500 ppm, and can be 1000 ppm. If the content of the higher fatty acid amide compound (e) is within the above range, the transparency and uniformity of the appearance of the multilayer film are excellent, and the variation of mechanical strength can be effectively suppressed, and therefore, the reliability as a packaging material can be improved.
[0102] As the higher fatty acid amide compound (e), there is no particular limitation as long as the melting point is 60 to 120°C. The lower limit of the melting point of the higher fatty acid amide compound (e) is preferably 70°C. The upper limit of the melting point of the higher fatty acid amide compound (e) is preferably 110°C. The melting point can be controlled according to the length of the carbon chain, the degree of unsaturation (the number of double bonds in the carbon chain), the number of amide groups, the presence or absence of other substituents, etc. As the higher fatty acid amide compound (e), saturated higher fatty acid bisamides, unsaturated higher fatty acid bisamides, saturated higher fatty acid monoamides, unsaturated higher fatty acid monoamides and their derivatives can be listed, preferably at least one selected from saturated higher fatty acid monoamides and unsaturated higher fatty acid monoamides having 10 to 25 carbon atoms. As saturated higher fatty acid monoamides having 10 to 25 carbon atoms, capric amide, lauryl amide, myristic amide, palmitamide, stearic amide, arachidamide, behenamide, etc. can be listed as preferred examples. Among these, from the viewpoint of economy and availability, lauramide, stearamide, behenamide are preferred, and stearamide is more preferred. As unsaturated higher fatty acid monoamides with 10 to 25 carbon atoms, from the viewpoint of suppressing coloration, monoolefin higher fatty acid monoamides with a degree of unsaturation of 1 are preferred, and oleamide, elaidic acid amide, isoleic acid amide, gadoleic acid amide, eicosenoic acid amide, erucic acid amide, etc. can be cited as preferred examples. Among these, from the viewpoint of economy and availability, oleamide and erucic acid amide are preferred. From the viewpoint of the thermal stability of the higher fatty acid amide compound (e), saturated higher fatty acid monoamides are preferred, and from the viewpoint of showing an effect within a wider range of processing conditions, unsaturated higher fatty acid monoamides are preferred. In addition, from the viewpoint of operability in the manufacturing and processing steps of the multilayer film, the carbon number of the higher fatty acid amide compound (e) is sometimes preferably 12 to 22. In addition, the higher fatty acid amide compound (e) may have substituents such as hydroxyl groups.
[0103] In one embodiment of the present invention, the higher fatty acid amide compound (e) preferably comprises two or more higher fatty acid amide compounds with different melting points. It is particularly preferred to comprise an unsaturated higher fatty acid amide compound (e1) having a melting point of 60°C or more and less than 90°C and a saturated higher fatty acid amide compound (e2) having a melting point of 90°C or more and less than 120°C. Thus, even in the case of large changes in temperature and humidity and more diverse storage environments, the change in the mechanical strength measurement value is sometimes reduced, and the stability of the mechanical strength can be more effectively improved.
[0104] <Inorganic Oxide Particles (f)>
[0105] The heat-sealed layer (D) preferably contains 500 to 5000 ppm of inorganic oxide particles (f) having an average particle size of 1 to 30 μm. If the heat-sealed layer (D) contains inorganic oxide particles (f) in the above range, the operability in the manufacturing and processing steps of the multilayer film is sometimes improved, and the stability of the mechanical strength of the multilayer film can be further improved. The average particle size of the inorganic oxide particles (f) is preferably 2 to 15 μm or more, and more preferably 3 to 10 μm or more. The average particle size is the median particle size measured by the light scattering method while circulating the obtained dispersion after dispersing the inorganic oxide particles (f) in water or an organic solvent and stirring them thoroughly. The content of the inorganic oxide particles (f) is preferably 750 to 4500 ppm, and more preferably 1000 to 4000 ppm. In addition, regarding the shape of the inorganic oxide particles (f), it is preferably a shape with a small aspect ratio and a nearly true spherical shape.
[0106] The inorganic oxide particles (f) are preferably at least one selected from silicon oxide particles and metal oxide particles. The metal constituting the metal oxide particles is preferably at least one selected from aluminum, magnesium, zirconium, cerium, tungsten, molybdenum, titanium and zinc. As the inorganic oxide constituting the inorganic oxide particles (f), specifically, silicon oxide, aluminum oxide, zirconium oxide, magnesium oxide, cerium oxide, tungsten oxide, molybdenum oxide, titanium oxide, zinc oxide and their composites (complexes of silicon oxide and aluminum oxide, etc.) can be listed, preferably silicon oxide.
[0107] The heat-welding layer (D) may contain other ingredients except ethylene-α-olefin copolymer resin (d), higher fatty acid amide compound (e) and inorganic oxide particles (f) as long as it does not hinder the effect of the present invention. As other ingredients, for example, alkali metal ions, polyvalent metal ions, carboxylic acids, phosphoric acid compounds, boron compounds, oxidation promoters, antioxidants, plasticizers, heat stabilizers (melt stabilizers), photoinitiators, deodorants, ultraviolet absorbers, antistatic agents, lubricants, colorants, fillers, desiccants, fillers, pigments, dyes, processing aids, flame retardants and antifogging agents can be listed. The content of other ingredients in the heat-welding layer (D) is usually 5% by mass or less, preferably 3% by mass or less, and more preferably 1% by mass or less. In addition, the heat-welding layer (D) may also contain a thermoplastic resin other than ethylene-α-olefin copolymer resin (d). As the thermoplastic resin, the above-mentioned resins exemplified as thermoplastic resins that can be included in the barrier layer (A) can be used. The content of the thermoplastic resin in the heat-sealing layer (D) is less than 50% by mass, preferably less than 30% by mass, more preferably less than 10% by mass, further preferably 5% by mass or less, and may be 1% by mass or less.
[0108] As the resin constituting the heat-welding layer (D), the proportion of the ethylene-α-olefin copolymer resin (d) is preferably 60% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, and may be 95% by mass or more, 97% by mass or more, or 99% by mass or more. The resin constituting the heat-welding layer (D) may consist of only the ethylene-α-olefin copolymer resin (d). In addition, the proportion of the ethylene-α-olefin copolymer resin (d) in the heat-welding layer (D) is preferably 60% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, and may be 95% by mass or more, 97% by mass or more, or 99% by mass or more. The heat-welding layer (D) may consist essentially of only the ethylene-α-olefin copolymer resin (d).
[0109] The manufacturing method of the resin composition constituting the heat-welding layer (D) is not particularly limited, and can be manufactured by melt-kneading ethylene-α-olefin copolymer resin (d) and other additives such as higher fatty acid amide compound (e) and inorganic oxide particles (f) as required. The higher fatty acid amide compound (e) can be blended in a solid state such as powder or in the form of a melt, or can be blended as a solute contained in a solution or a dispersoid contained in a dispersion. As a solution and a dispersion, an aqueous solution and an aqueous dispersion are suitable, respectively. For melt-kneading, a known mixing device or a mixing device such as a kneading extruder, an extruder, an open roll, a Banbury mixer, etc. can be used. The temperature range during melt-kneading can be appropriately adjusted according to the melting point of the ethylene-α-olefin copolymer resin (d) used, and is generally 150 to 300°C.
[0110] In addition, in another mode, a masterbatch can be produced by melt-kneading to make ethylene-α-olefin copolymer resin (d) contain other additives such as higher fatty acid amide compound (e) and inorganic oxide particles (f) at high concentration as required, and the masterbatch is dry-mixed with ethylene-α-olefin copolymer resin (d) substantially free of other additives such as higher fatty acid amide compound (e) and inorganic oxide particles (f), and used to manufacture multilayer film. In addition, in another mode, ethylene-α-olefin copolymer resin (d) and other additives such as higher fatty acid amide compound (e) and inorganic oxide particles (f) as required can be used to manufacture multilayer film by dry mixing. Dry mixing refers to mechanical mixing in the form of powder or pellet. Mixing can be carried out using mixing devices such as rotary drum, ribbon stirrer, Henschel mixer, etc., or by manually stirring, shaking, etc. in a closed container. As the mixing temperature, it can be carried out under the condition of room temperature to lower than the melting point of ethylene-α-olefin copolymer resin (d), and mixing can be carried out under air atmosphere or nitrogen atmosphere.
[0111] <Multilayer Film>
[0112] The multilayer film of the present invention has a barrier layer (A), an adhesive layer (B), a thermoplastic resin layer (C) and a heat-sealed layer (D), and on the other hand, does not have a layer containing a resin with a melting point of 200°C or more as a main component and a metal layer with a thickness of 1 μm or more. By not having a layer containing a resin with a melting point of 200°C or more as a main component and a metal layer with a thickness of 1 μm or more, when the crushed product of the multilayer film is melt-molded, it is possible to suppress the mixing with other components from becoming uneven. It should be noted that the metal layer here refers to a layer having a continuous surface and a discontinuous surface formed by a metal, such as aluminum foil. In addition, it is preferred that at least one group of barrier layers (A) is stacked adjacent to the adhesive layer (B). In this way, a multilayer film having high gas barrier properties and recyclability, and excellent mechanical strength and stability can be obtained.
[0113] Regarding the multilayer film of the present invention, when the temperature is increased from -50°C to 220°C (first temperature increase) at 10°C / min using a differential scanning calorimeter (DSC), then the temperature is lowered to -50°C at 10°C / min, and then the temperature is increased to 220°C (second temperature increase) at 10°C / min, the ratio (H1 / H2) of the total heat of fusion (H1) at 0 to 150°C during the first temperature increase to the total heat of fusion (H2) at 0 to 150°C during the second temperature increase is 0.75 to 1.01. By setting the ratio of the heat of fusion (H1 / H2) to the above range, the total thickness can be suppressed, and the mechanical strength and water vapor barrier properties can be achieved at a high level. From the viewpoint of further improving the mechanical strength, the upper limit of the ratio of the heat of fusion (H1 / H2) is preferably 0.99, more preferably 0.97, and even more preferably 0.95. On the other hand, from the viewpoint of improving the water vapor barrier property of the multilayer film, the lower limit of the above-mentioned ratio of heat of fusion (H1 / H2) is preferably 0.85, more preferably 0.90, and further preferably 0.92. Here, the total heat of fusion at 0 to 150°C refers to the total heat of fusion of the resin having a melting point of 0 to 150°C in the multilayer film, and in one embodiment of the present invention, for example, refers to the total heat of fusion of the polyethylene resin. The above-mentioned ratio of heat of fusion (H1 / H2) can be controlled by the set temperature of the extruder and the die when the multilayer film is manufactured and the cooling rate after ejection from the die. In the case of using a T die (casting molding, etc.), the cooling rate after ejection from the die can be controlled by the distance (air gap) or time from the ejection from the die to the initial contact with the cooling roller or the temperature of the cooling roller, and it is especially important to reduce the crystallinity by quenching. The temperature of the cooling roller is preferably 35°C to 75°C, more preferably 35°C to 65°C, and further preferably 35°C to 50°C. On the other hand, when using an annular mold (inflation molding, blow molding, etc.), the cooling means are limited, it is difficult to perform rapid cooling, and it is difficult to meet the above-mentioned melting heat ratio (H1 / H2). In addition, when heat treatment is performed again after temporary cooling, it can also be controlled by its temperature and time.
[0114] Regarding the multilayer film of the present invention, when the temperature is increased from -50°C to 220°C (first temperature increase) at 10°C / min using a differential scanning calorimeter (DSC), then the temperature is lowered to -50°C at 10°C / min, and then the temperature is increased to 220°C (second temperature increase) at 10°C / min, the ratio (H1 / H2) of the total heat of fusion (H1) at 150 to 200°C during the first temperature increase to the total heat of fusion (H2) at 150 to 200°C during the second temperature increase is preferably 0.90 to 1.35. By setting the ratio of the heat of fusion (H1 / H2) to the above range, the total thickness can be suppressed, and the mechanical strength and oxygen barrier properties can be taken into account at a higher level. From the viewpoint of further improving the mechanical strength, the upper limit of the ratio of the heat of fusion (H1 / H2) is more preferably 1.30, and more preferably 1.25. On the other hand, from the viewpoint of improving the oxygen barrier property of the multilayer film, the lower limit of the above-mentioned heat of fusion ratio (H1 / H2) is more preferably 1.00, and further preferably 1.10. Here, the total heat of fusion at 150 to 200°C refers to the total heat of fusion of the resin having a melting point of 150 to 200°C in the multilayer film, and in one embodiment of the present invention, for example, refers to the total heat of fusion of EVOH (a). The above-mentioned heat of fusion ratio (H1 / H2) can be controlled by the set temperature of the extruder and the die when the multilayer film is manufactured and the cooling rate after ejection from the die. The barrier layer (A) containing EVOH (a) is arranged between at least one set of thermoplastic resin layer (C) and the heat-sealing layer (D), and therefore, it is not easily affected by, for example, a cooling roll. By setting the cooling roll to a sufficiently low temperature, the barrier layer (A) can be effectively cooled, and the above-mentioned heat of fusion ratio (H1 / H2) can be more effectively adjusted to the above-mentioned range. When a T-mold is used, the cooling rate after ejection from the mold can be controlled by the distance (air gap) or time from ejection from the mold to contact with the initial cooling roller or the temperature of the cooling roller, and it is especially important to reduce the crystallinity by quenching. On the other hand, when an annular mold is used (inflation molding, blow molding, etc.), the cooling means are limited, and it is difficult to quench, and it is difficult to meet the above-mentioned ratio of heat of fusion (H1 / H2). In addition, in the case of temporarily cooling and then performing heat treatment again, it can also be controlled by its temperature and time, etc.
[0115] As a lamination method for manufacturing the above-mentioned multilayer film, the existing co-extrusion method of extruding and laminating various resins from respective molds or a common mold can be used. As the mold, either a ring mold or a T mold can be used. The molding temperature during melt molding can be appropriately adjusted according to the melting point and melt viscosity of the resin used, and is mostly selected from the range of 150 to 300°C.
[0116] The total thickness of the multilayer film of the present invention is preferably 15 to 300 μm, more preferably 25 to 250 μm, further preferably 35 to 200 μm, and particularly preferably 45 to 150 μm. By making the total thickness within the above range, the multilayer film of the present invention is light and flexible, and therefore, is preferably used for flexible packaging. In addition, the amount of resin used in the multilayer film is small, which can suppress environmental burden.
[0117] The ratio of the thickness of the barrier layer (A) in the multilayer film of the present invention to the total thickness of all layers is preferably 0.10 or less. If the ratio is within the above range, recyclability and mechanical strength are improved. The upper limit of the ratio of the thickness of the barrier layer (A) to the total thickness of all layers is more preferably 0.08 or less, further preferably 0.05 or less, and particularly preferably 0.04 or less. The lower limit of the ratio of the thickness of the barrier layer (A) to the total thickness of all layers is not particularly limited, and in order to exhibit sufficient gas barrier properties, it is usually 0.005 or more. On the other hand, the ratio of the thickness of the thermoplastic resin layer (C) in the multilayer film of the present invention to the total thickness of all layers is preferably 0.20 or more and 0.60 or less. If the ratio is within the above range, the water vapor barrier properties of the multilayer film are improved. In addition, the total ratio of the thickness of the thermoplastic resin layer (C) and the thickness of the heat-sealed layer (D) relative to the total thickness of all layers in the multilayer film of the present invention is preferably 0.60 or more, more preferably 0.70 or more, and more preferably 0.80 or more. When the ratio is within the above range, recyclability, mechanical strength, and water vapor barrier properties are improved.
[0118] The layer structure of the multilayer film of the present invention is not particularly limited as long as there is a barrier layer (A) between at least one set of thermoplastic resin layers (C) and thermoplastic resin layers (D). If the thermoplastic resin layer (C) is represented by (C), the adhesive resin layer (B) is represented by (B (B1 or B2)), the barrier layer (A) is represented by (A), and the heat-sealing layer (D) is represented by (D), and " / " is used to represent direct lamination, for example, layer structures such as (C) / (B1) / (A) / (B2) / (D) and (C) / (D) / (B2) / (A) / (B2) / (D) can be listed. In addition to the above layer structure, other layers may be further included, and the other layers may be present in the outermost layer of the above multilayer film or between the layers. The multilayer film of the present invention has a barrier layer (A) between at least one set of thermoplastic resin layers (C) and heat-sealing layers (D), so that the cooling of the thermoplastic resin layer (C) and the heat-sealing layer (D) after film formation can be effectively performed, and the total heat of fusion ratio (H1 / H2) at 0 to 150°C can be adjusted relatively easily. In addition, when a plurality of any of the barrier layer (A), the adhesive layer (B) and the heat-sealing layer (D) are used, different types of resins can be used respectively. It should be noted that, when the thermoplastic resin layer (C) and the adhesive layer (B) are directly laminated, if the acid value of the adhesive layer (B) is a low value, the appearance characteristics of the obtained multilayer film tend to be excellent. On the other hand, when the heat-sealing layer (D) and the adhesive layer (B) are directly laminated, the acid value of the adhesive layer (B) has little effect on the appearance characteristics of the obtained multilayer film, and if the acid value is a certain range, the appearance characteristics are excellent. From the viewpoint of being able to more easily adjust the total heat of fusion ratio (H1 / H2) at 0 to 150°C, it is preferred that one outermost layer is a thermoplastic resin layer (C) and the other outermost layer is a heat-sealing layer.
[0119] The oxygen permeation rate (OTR) of the multilayer film of the present invention at 20°C and 65% RH can be adjusted according to the application and is not particularly limited, but is preferably 5 cc / (m 2 The multilayer film with OTR in this range has excellent gas barrier properties and is suitable for use as a packaging material. The OTR is more preferably 4 cc / (m 2 ·day·atm) or less, more preferably 3cc / (m 2 ·day·atm) or less, particularly preferably 2cc / (m 2 OTR is measured in accordance with JIS K 7126-2 (isobaric method; 2006), specifically, the method described in Examples is used.
[0120] The water vapor transmission rate (WVTR) of the multilayer film of the present invention at 40°C and 90% RH can be adjusted according to the application and is not particularly limited, but is preferably 4.5 g / (m 2 The multilayer film with WVTR in this range has excellent gas barrier properties and is suitable for use as a packaging material. The WVTR is more preferably 4.0 g / (m 2 ·day) or less, more preferably 3.5g / (m 2 ·day) or less, particularly preferably 3.0g / (m 2 WVTR is measured in accordance with JIS K 7129-2 (infrared sensor method; 2019), specifically, the method described in the Examples.
[0121] The multilayer film of the present invention is humidified at 23°C and 50% RH for 24 hours, and the elongation at break (puncture elongation at break) when punctured at a speed of 50 mm / min with a needle having a front end diameter of 1 mm under the same conditions is preferably 8.0 mm or more. The multilayer film having a puncture elongation at break in this range has excellent mechanical strength and is not easily broken by external impact, etc., and is therefore suitable for use as a packaging material. The puncture elongation is more preferably 9.0 mm or more, further preferably 10.0 mm or more, and particularly preferably 11.0 mm or more. The puncture elongation can be 16.0 mm or less.
[0122] The multilayer film of the present invention is preferably 8.5N or more when punctured by a needle with a tip diameter of 1 mm at a speed of 50 mm / min under the same conditions after humidity conditioning for 24 hours at 23°C and 50% RH. The multilayer film having a puncture strength in this range has excellent mechanical strength and is not easily broken by external impact, etc., and is therefore suitable for use as a packaging material. The puncture elongation is more preferably 9.0N or more, further preferably 10.0N or more, and particularly preferably 10.5N or more. The puncture strength can be 15.0N or less.
[0123] The coefficient of variation (the value obtained by dividing the standard deviation by the average value) of the puncture fracture strength of the multilayer film of the present invention is preferably 0.05 or less. The multilayer film having a coefficient of variation within this range has excellent stability in mechanical strength and is not easily broken by external impact, etc., and is therefore suitable for use as a packaging material. The coefficient of variation is more preferably 0.03 or less, further preferably 0.015 or less, and particularly preferably 0.010 or less.
[0124] <Multilayer structure>
[0125] The multilayer film of the present invention can be used as a packaging material having gas barrier properties. By forming a multilayer structure in which at least one resin layer (R) containing a thermoplastic resin (h) as a main component is laminated, various functions as a packaging material such as heat resistance and design properties can be imparted. The thermoplastic resin (h) is not particularly limited, and examples thereof include homopolymers or copolymers of olefins such as linear low-density polyethylene, low-density polyethylene, medium-density polyethylene, high-density polyethylene, vinyl ester resins, ethylene-propylene copolymers, polypropylene, propylene-α-olefin copolymers (α-olefins having 4 to 20 carbon atoms), polybutene, and polypentene; polyamides such as nylon 6 and nylon 6,6; polyesters such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polystyrene, polyvinyl chloride, polyvinylidene chloride, acrylic resins, polycarbonate, chlorinated polyethylene, and chlorinated polypropylene. Among them, from the viewpoint of excellent moisture resistance, mechanical properties, heat sealability, economy, etc., polyolefins are preferred, and from the viewpoint of excellent mechanical properties, heat resistance, etc., polyamides and polyesters are preferred. In particular, in order to obtain a multilayer structure with excellent reusability, the thermoplastic resin (h) more preferably contains a polyethylene resin as the main component, and is further preferably a polyethylene resin. The resin layer (R) can be a single layer or a multilayer comprising a plurality of layers. In addition, the resin layer (R) can be unstretched, or it can be stretched or calendered along a uniaxial direction or a biaxial direction. From the viewpoint of improving mechanical strength, a biaxially stretched layer is preferred, and from the viewpoint of improving heat sealability, an unstretched layer is preferred.
[0126] The film-making method of the resin layer (R) is not particularly limited, and the film is generally made by melt extrusion using an extruder. As a mold, any of a ring mold or a T mold can be used. The method of stretching along a uniaxial direction or a biaxial direction is also not particularly limited. It can be manufactured by stretching along the flow direction of the film and / or the direction perpendicular to the flow direction, that is, the width direction, using existing known stretching methods such as roller uniaxial stretching, tubular simultaneous biaxial stretching, tenter-type sequential biaxial stretching, and tenter-type simultaneous biaxial stretching. With regard to the stretching ratio, from the perspective of the thickness uniformity and mechanical strength of the obtained layer, it is preferred that the area ratio be set to 8 to 60 times. The area ratio is more preferably 55 times or less, and further preferably 50 times or less. In addition, the area ratio is more preferably 9 times or more. If the area ratio is less than 8 times, residual stretching unevenness is sometimes left, and if it exceeds 60 times, the layer is sometimes prone to breakage during stretching.
[0127] From the viewpoint of industrial productivity, the thickness of the resin layer (R) is preferably 10 to 200 μm. Specifically, the thickness of the unstretched layer is more preferably 10 to 150 μm, and the thickness of the biaxially stretched layer is more preferably 10 to 50 μm.
[0128] In addition, the total thickness of the multilayer structure of the present invention is preferably 300 μm or less, and may be 25 μm or more. By making the total thickness within the above range, the multilayer structure of the present invention maintains good mechanical properties and gas barrier properties, while being lightweight and flexible, and is therefore preferably used for soft packaging. In addition, the amount of resin used in the multilayer structure is small, which can suppress environmental burden.
[0129] The thickness of each layer in the multilayer structure of the present invention can be appropriately adjusted depending on the application. From the viewpoint of suppressing coloration when the pulverized material is melt-molded, improving thermal stability during melt molding, and suppressing the generation of pitting, the ratio of the total thickness of the layers containing the polyethylene resin (resin layer (R), adhesive layer (B), thermoplastic resin layer (C) and heat-sealing layer (D)) as the main component to the total thickness of the multilayer structure is preferably 0.80 or more, more preferably 0.85 or more, further preferably 0.90 or more, and particularly preferably 0.95 or more.
[0130] The multilayer structure of the present invention preferably does not have a layer containing a resin having a melting point of 200°C or more as a main component and a metal layer having a thickness of 1 μm or more. By not having a layer containing a resin having a melting point of 200°C or more as a main component and a metal layer having a thickness of 1 μm or more, when the pulverized product of the multilayer structure is melt-molded, it is possible to suppress the mixing with other components from becoming uneven. It should be noted that the metal layer here refers to a layer having a continuous surface and a discontinuous surface formed of a metal, such as aluminum foil.
[0131] The method of laminating the resin layer (R) of the multilayer film of the present invention is not particularly limited, and examples thereof include extrusion lamination, coextrusion lamination, dry lamination, etc. When laminating the resin layer (R) of the multilayer film, an adhesive layer may be provided. The adhesive layer may use an adhesive layer (B), which may be formed by applying a known adhesive and drying. The adhesive is preferably a two-component reactive polyurethane adhesive in which a polyisocyanate component and a polyol component are mixed and reacted. The thickness of the adhesive layer is not particularly limited, and is preferably 1 to 5 μm, and more preferably 2 to 4 μm.
[0132] The multilayer structure of the present invention may have other layers other than those described above within the scope that does not hinder the effect of the present invention. As an example of other layers, a recycling layer can be cited. In particular, it is preferred that the recycled composition containing the recycled material of the multilayer film or multilayer structure of the present invention described later is used again as part or all of the recycling layer. As another example of other layers, for example, a printing layer can be cited. The printing layer can be included in any position of the multilayer structure of the present invention. As a printing layer, for example, a coating obtained by coating a solution containing a pigment or dye and a binder resin as required and drying can be cited. As a coating method for the printing layer, in addition to the gravure printing method, various coating methods using a wire rod, a spin coater, a die coater, etc. can be cited. The thickness of the printing layer is not particularly limited, preferably 0.5 to 10 μm, more preferably 1 to 4 μm.
[0133] It is preferred that the ends and defective products generated when manufacturing the multilayer film and multilayer structure of the present invention are recycled and reused. In addition, recycling and reusing the multilayer film and multilayer structure circulated in the market is also a suitable embodiment. The recycling method of the multilayer film and multilayer structure of the present invention, which is crushed and then melt-molded, and the recycling composition containing the recycled products of the multilayer film and multilayer structure of the present invention are also suitable embodiments of the present invention. Here, the recycled products of the multilayer film and multilayer structure of the present invention also include recycled products of packaging materials containing the multilayer film or multilayer structure of the present invention.
[0134] When the multilayer film and multilayer structure of the present invention are recovered, first, the recycled material of the multilayer film and multilayer structure of the present invention is crushed. The crushed recycled material can be directly melt-molded to obtain a recycled composition, or it can be melt-molded together with other components as needed to obtain a recycled composition. As a preferred component added to the recycled material, a polyolefin resin is preferred, and a polyethylene resin is more preferred. The crushed recycled material can be directly used to manufacture molded products such as multilayer structures, or the crushed recycled material can be melt-granulated to obtain pellets containing the recycled composition, and then the pellets are used to manufacture molded products. As a melt molding method for the recycled composition, extrusion molding, inflation extrusion, blow molding, melt spinning, injection molding, etc. The molding temperature during melt molding can be appropriately adjusted according to the melting point and melt viscosity of the resin used, and is mostly selected from the range of 150 to 300°C. The aforementioned recycled composition may contain unused resin, and the content of the recycled material in the recycled composition is preferably 10% by mass or more, more preferably 20% by mass or more, and can be 30% by mass or more. The content of EVOH (a) in the recovered composition is preferably 20% by mass or less, more preferably 10% by mass or less, and may be 5% by mass or less.
[0135] The multilayer structure of the present invention has excellent appearance characteristics, gas barrier properties, mechanical properties and recyclability, and can therefore be suitably used as a material for various packaging such as food packaging, pharmaceutical packaging, industrial chemical packaging, and pesticide packaging, and can be used in a wider range of applications, but is not limited to these applications.
[0136] A package body formed by filling the aforementioned packaging material with contents is a suitable embodiment of the aforementioned packaging material. Examples of the contents that can be filled include beverages such as wine and juice; foods such as fruits, nuts, vegetables, meat products, infant foods, coffee, jams, mayonnaise, ketchup, cooking oils, sauces, soups, salted and seafood products, and dairy products; and other contents that are easily degraded in the presence of oxygen such as medicines, cosmetics, and gasoline, but are not limited thereto.
[0137] Example
[0138] Hereinafter, the present invention will be described in more detail using Examples, but the present invention is not limited to these Examples at all.
[0139] <Materials used>
[0140] Adhesive resin (b)
[0141] b-1: maleic anhydride-modified polyethylene "ADMER (trademark) NF518" manufactured by Mitsui Chemicals, Inc. (MFR (190°C, 2.16 kg load) is 3.1 g / 10 min, density is 0.91 g / cm 3 , acid value is 1.10mgKOH / g)
[0142] b-2: maleic anhydride-modified polyethylene "BYNEL (trademark) 41E687" manufactured by Dow Chemical Co. (MFR (190°C, 2.16 kg load) 1.7 g / 10 min, density 0.91 g / cm 3 , acid value is 2.75mgKOH / g)
[0143] b-3: The linear low-density polyethylene (d-1) described below was mixed with maleic anhydride-modified polyethylene "BYNEL (trademark) 41E710" (MFR (190°C, 2.16 kg load) of 1.7 g / 10 min, density of 0.91 g / cm 3 , acid value is 10.7mgKOH / g) are dry mixed at a mass ratio of 85 / 15 (average acid value is 1.6mgKOH / g)
[0144] Polyethylene resin (c)
[0145] c-1: High-density polyethylene "NOVATEC (trademark) HD HY540" manufactured by Japan Polyethylene Co., Ltd. (MFR (190°C, 2.16 kg load) is 1.0 g / 10 minutes, density is 0.960 g / cm 3 )
[0146] c-2: High-density polyethylene "HI-ZEX (trademark) 3300F" manufactured by Prime Polymer Co., Ltd. (MFR (190°C, 2.16 kg load) is 1.1 g / 10 min, density is 0.949 g / cm 3 )
[0147] Ethylene-α-olefin copolymer resin (d)
[0148] d-1: linear low-density polyethylene, "ELITE (trademark) AT6101" manufactured by Dow Chemical (polymerization of ethylene and 1-octene using a metallocene catalyst, MFR (190°C, 2.16 kg load) of 0.8 g / 10 min, density of 0.905 g / cm 3 , the heat of fusion below 100°C is 69.2 J / g, the heat of fusion above 100°C is 17.6 J / g, the total heat of fusion is 86.8 J / g, and the ratio of the heat of fusion below 100°C is 79.7%)
[0149] d-2: linear low-density polyethylene "EVOLUE (trademark) SP0510" manufactured by Prime Polymer Co., Ltd. (polymerized ethylene and 1-hexene using a metallocene catalyst, MFR (190°C, 2.16 kg load) of 1.2 g / 10 min, density of 0.903 g / cm 3 , the heat of fusion below 100°C is 61.6 J / g, the heat of fusion above 100°C is 20.9 J / g, the total heat of fusion is 82.5 J / g, and the ratio of the heat of fusion below 100°C is 74.7%)
[0150] d-3: low-density polyethylene "NOVATEC (trademark) LD LJ400" manufactured by Japan Polyethylene Co., Ltd. (not ethylene-α-olefin copolymer, MFR (190°C, 2.16 kg load) is 1.5 g / 10 min, density is 0.921 g / cm 3 , the heat of fusion below 100°C is 51.7 J / g, the heat of fusion above 100°C is 59.5 J / g, the total heat of fusion is 111.2 J / g, and the ratio of the heat of fusion below 100°C is 46.5%)
[0151] d-4: linear low-density polyethylene "INNATE (trademark) TH60" manufactured by Dow Chemical (polymerized ethylene and 1-octene, MFR (190°C, 2.16 kg load) of 0.85 g / 10 min, density of 0.912 g / cm 3 , the heat of fusion below 100°C is 30.5 J / g, the heat of fusion above 100°C is 56.2 J / g, the total heat of fusion is 86.7 J / g, and the ratio of the heat of fusion below 100°C is 35.2%)
[0152] The heat of fusion below 100°C, the heat of fusion above 100°C, the total heat of fusion and the ratio of the heat of fusion below 100°C for d-1 to d-4 were calculated based on the melting curve when the temperature was increased from 20°C to 250°C at a rate of 10°C / min using a differential scanning calorimeter DSC ("Q2000" manufactured by TA Instrument).
[0153] Higher fatty acid amide compound (e)
[0154] S1A: stearamide (melting point 101°C)
[0155] O1A: Oleic acid amide (melting point 72°C)
[0156] ·Multivalent metal ions (g)
[0157] Mg-St: Magnesium Stearate
[0158] Ca-St: Calcium Stearate
[0159] Zn-St: Zinc Stearate
[0160] MgOAc: magnesium acetate
[0161] Alkali metal ions
[0162] AcONa: Sodium acetate
[0163] AcOK: Potassium acetate
[0164] <Evaluation method>
[0165] (1) Heat of fusion analysis
[0166] For the multilayer films obtained in the embodiments and comparative examples, a differential scanning calorimeter DSC ("Q2000" manufactured by TA Instrument) was used to increase the temperature from -50°C to 220°C at 10°C / min (first temperature increase), then cool to -50°C at 10°C / min, and then increase the temperature to 220°C at 10°C / min (second temperature increase), and the ratio (H1 / H2) of the total heat of fusion at 0 to 150°C during the first temperature increase (H1) to the total heat of fusion at 0 to 150°C during the second temperature increase (H2) was calculated.
[0167] (2) Evaluation of appearance characteristics
[0168] The multilayer films obtained in Examples and Comparative Examples were visually evaluated and judged according to the following criteria: E1 to E3 were unacceptable criteria.
[0169] Judgment: Benchmark
[0170] A: Uniform appearance, no coloring, good
[0171] B1: Very slight defects such as pitting are observed
[0172] B2: Very slight coloration (yellowing) was observed
[0173] B3: Very slight unevenness (thickness, bleeding) was observed
[0174] C1: Minor defects such as pitting were observed
[0175] C2: Slight coloration (yellowing) observed
[0176] C3: Slight unevenness (thickness, bleeding) was observed
[0177] D1: Moderate defects such as pitting were observed
[0178] D2: Moderate coloration (yellowing) observed
[0179] D3: Moderate unevenness (thickness, bleeding) observed
[0180] E1: Severe defects such as pitting are observed
[0181] E2: Severe coloration (yellowing) observed
[0182] E3: Severe unevenness (thickness, exudation) observed
[0183] (3) Oxygen permeability measurement
[0184] The multilayer films obtained in the examples and comparative examples were used, with one side being the oxygen supply side and the other side being the carrier gas side, to measure the oxygen permeation rate. Specifically, an oxygen permeation rate measuring apparatus ("MOCON OX-TRAN2 / 21" manufactured by Modern Controls) was used in accordance with JIS K 7126-2 (isobaric method; 2006) under the conditions of a temperature of 20°C, a humidity of 65% RH on the oxygen supply side, a humidity of 65% RH on the carrier gas side, an oxygen pressure of 1 atm, and a carrier gas pressure of 1 atm, to measure the oxygen permeation rate (unit: cc / (m 2 ·day·atm)). Nitrogen containing 2 vol% of hydrogen was used as carrier gas.
[0185] (4) Water vapor transmission rate measurement
[0186] The multilayer films obtained in the examples and comparative examples were used, with one side set as the water vapor supply side and the other side set as the carrier gas side, to measure the water vapor permeation rate. Specifically, a water vapor permeation rate measuring device ("MOCON PERMATRAN W3 / 33" manufactured by Modern Controls) was used in accordance with JIS K 7129-2 (infrared sensor method; 2019), at a temperature of 40°C, a humidity of 90% RH on the water vapor supply side, and a humidity of 0% RH on the carrier gas side, to measure the oxygen permeation rate (unit: g / (m 2 ·day)). Nitrogen was used as carrier gas. The water vapor transmission rate was 4.5 g / (m 2 · days) or more, it was judged that the water vapor barrier property was insufficient.
[0187] (5) Puncture breaking strength and elongation measurement
[0188] After the multilayer film obtained in the embodiment and the comparative example was humidified at 23°C and 50% RH for 24 hours, it was punctured at a speed of 50 mm / min with a needle with a front diameter of 1 mm under the same conditions to measure the elongation at break and the breaking strength at this time. The measurement was performed 10 times while changing the location, and the average value was used as the measurement result. When the elongation at break after puncture is less than 8.0 mm, it is judged that the mechanical properties are insufficient. In addition, when the puncture breaking strength is less than 8.5 N, it is judged that the mechanical properties are insufficient.
[0189] (6) Evaluation of bag breakage resistance
[0190] The multilayer film obtained in the embodiment and the comparative example is cut into 2 pieces of A4 size and overlapped, and the 3 sides are heat-sealed with a width of 5mm. Then, after filling 1L of water from the opening, the remaining sides are heat-sealed to make a water-filled bag. The water-filled bag is allowed to fall freely from a height of 1m in an upright direction under the conditions of 20°C and 70%RH. It is allowed to fall 20 times. If no water leakage and interlayer peeling are observed, it is considered qualified. If leakage or interlayer peeling is observed, it is considered unqualified. Carry out the same test 5 times and judge according to the following criteria. It should be noted that C is an unacceptable criterion.
[0191] Judgment: Benchmark
[0192] A: All 5 times are qualified
[0193] B: 4 out of 5 times passed and 1 failed
[0194] C: Failed more than 2 times
[0195] (7) Pockmarks and coloration of a melt-molded product of a multilayer film
[0196] The multilayer films obtained in the examples and comparative examples were crushed into a size of 4 mm or less. The crushed product was mixed with a low-density polyethylene resin "NOVATECLD LJ400" (MFR (190°C, 2.16 kg load) made by Japan Polyethylene Co., Ltd. (MFR (190°C, 2.16 kg load) is 1.5 g / 10 minutes, density is 0.921 g / cm 3 ) were blended at a mass ratio (crushed product / polyethylene resin) of 40 / 60, and a single-layer film was formed using the extrusion conditions shown below, thereby obtaining a single-layer film with a thickness of 50 μm. The thickness of the single-layer film was adjusted by appropriately changing the screw speed and the pulling roll speed. In addition, as a control, a single-layer film with a thickness of 50 μm was obtained using only polyethylene resin.
[0197] Extruder: Single screw extruder manufactured by Toyo Seiki Co., Ltd.
[0198] Screw diameter: (L / D=20, compression ratio=3.5, full thread type)
[0199] Extrusion temperature: supply part / compression part / metering part / die = 180 / 230 / 230 / 230℃
[0200] Pulling roller temperature: 80℃
[0201] The pitting and coloration of the obtained single layer film were evaluated according to the following five levels A to E. It should be noted that E was considered unacceptable.
[0202] Criteria for judging pitting
[0203] A: Compared with the control, the amount of pitting is almost unchanged
[0204] B: Compared with the control, the amount of small pockmarks is slightly more
[0205] C: Compared with the control, the number of small pockmarks is more
[0206] D: Compared with the control, the amount of cannabis spots is more
[0207] E: Compared with the control, the amount of cannabis dots is very high
[0208] Coloring Criteria
[0209] A: The degree of hue change is small compared to the control
[0210] B: Slight coloration was observed compared to the control
[0211] C: Moderate coloration observed compared to the control
[0212] D: Significant coloration was observed compared to the control
[0213] E: Compared with the control, significant coloration was observed, and unevenness was also observed
[0214] (8) Melt viscosity stability of crushed multilayer film
[0215] The multilayer film obtained in the examples and comparative examples was crushed into a size of 4 mm square or less. 60 g of the crushed material was kneaded under a nitrogen atmosphere at 230°C and 100 rpm using LABOPLASTMIL (biaxial anisotropy), and the torque change at this time was measured. The torque values (TI and TF, respectively) were calculated 10 minutes after the start of kneading and 90 minutes after the start of kneading, and the evaluation was performed according to the following 5 stages A to E based on the ratio of the values (TF / TI). It should be noted that E is an unacceptable benchmark.
[0216] Judgment Criteria
[0217] A: 80 / 100 or more and less than 120 / 100
[0218] B: 70 / 100 or more and less than 80 / 100 or 120 / 100 or more and less than 130 / 100
[0219] C: 60 / 100 or more and less than 70 / 100 or 130 / 100 or more and less than 140 / 100
[0220] D: 50 / 100 or more and less than 60 / 100 or 140 / 100 or more and less than 150 / 100
[0221] E: less than 50 / 100 or 150 / 100 or more
[0222] (Example)
[0223] Example 1
[0224] Water-containing pellets of EVOH (a-1) (ethylene unit content of 32 mol%, saponification degree of 99.9 mol%, MFR (190°C, 2.16 kg load) of 1.6 g / 10 minutes when dried) were put into an aqueous solution containing sodium acetate, phosphoric acid and boric acid, and immersed while stirring at 25°C for 6 hours, and then dehydrated, and dried at 80°C for 4 hours using a hot air dryer ("DN6101" manufactured by Yamato Scientific Co., Ltd.), and then dried at 120°C for 40 hours to obtain dry EVOH pellets (water content of 0.25%). It should be noted that the concentrations of sodium acetate, phosphoric acid and boric acid were adjusted as follows: sodium acetate was 200 ppm in terms of sodium ion, phosphate ion was 30 ppm in terms of phosphate, and boric acid was 150 ppm in terms of boron element in terms of content in the obtained dry EVOH pellets. The obtained dried EVOH pellets and magnesium stearate were melt-kneaded so that the content of magnesium ions in the obtained resin composition was 50 ppm to obtain resin composition pellets for barrier layer (A). The melt-kneading was performed using a twin-screw extruder (D (mm) = 25, L / D = 30, screw: co-rotating fully intermeshing type) manufactured by Toyo Seiki Seisaku-sho, Ltd., so that the resin temperature was 220°C.
[0225] The pellets of linear low-density polyethylene (d-1) "ELITE (trademark) AT6101" and stearamide (S1A) (melting point 101°C) were melt-kneaded so that the content of stearamide in the obtained resin composition was 4% by mass to produce stearamide masterbatch pellets. The melt-kneading was performed using a twin-screw extruder (D (mm) = 25, L / D = 30, screw: co-rotating fully meshing type) manufactured by Toyo Seiki Seisaku-sho, Ltd., so that the resin temperature was 220°C. Next, the pellets of linear low-density polyethylene (d-1) and the obtained stearamide masterbatch pellets were dry-blended at a mass ratio of 98 / 2 to obtain pellets of a resin composition for the heat-sealing layer (D).
[0226] The resin composition pellets for the barrier layer (A) obtained above, maleic anhydride-modified polyethylene (b-1) manufactured by Mitsui Chemicals used in the adhesive layer (B), HDPE (c-1) manufactured by Japan Polyethylene Co., Ltd. used in the thermoplastic resin layer (C), and the resin composition pellets for the heat-welding layer (D) obtained above were used, and a 300 mm wide 5-layer co-extrusion casting film-making equipment was used to produce a multilayer film having a layer thickness and layer structure of (C) / (B1) / (A) / (B2) / (D) = 51 μm / 6 μm / 6 μm / 6 μm / 51 μm. The film-making conditions at this time are shown below.
[0227] Extrusion temperature of barrier layer (A): supply part / compression part / metering part / die = 170 / 220 / 220 / 220°C
[0228] Extrusion temperature of adhesive layers (B1) and (B2): supply part / compression part / metering part / die = 170 / 220 / 220 / 220°C
[0229] Extrusion temperature of the thermoplastic resin layer (C): supply section / compression section / metering section / die = 170 / 220 / 220 / 220°C
[0230] Extrusion temperature of heat-sealing layer (D): supply part / compression part / metering part / die = 170 / 220 / 220 / 220°C
[0231] Distance from mold to cooling roller (air gap): 7 cm
[0232] Temperature of cooling roller: 40℃
[0233] Traction speed: 1.5m / min
[0234] The obtained multilayer film was evaluated for heat of fusion analysis, appearance characteristics evaluation, oxygen permeation rate, water vapor permeation rate, puncture breaking strength, bag breakage resistance, pitting and coloration of the melt-molded product of the pulverized product of the multilayer film, and melt viscosity stability of the pulverized product of the multilayer film according to the methods described in the above evaluation methods (1) to (8). The results are shown in Table 3.
[0235] A two-component reactive polyurethane adhesive (24 parts by mass of "TAKELAC A-520" and 4 parts by mass of "TAKENATEA-50" manufactured by Mitsui Chemicals, Inc.) was mixed with 37 parts by mass of ethyl acetate to prepare an adhesive solution. Next, the adhesive solution was applied to a uniaxially stretched polyethylene film (resin layer (R)) having a thickness of 25 μm using a bar coater so that the thickness after drying became 2 μm, and the film was dried at 100°C for 5 minutes, and laminated with the multilayer film obtained above to prepare a multilayer structure having a layer thickness and a layer structure of (R) / adhesive / (C) / (B1) / (A) / (B2) / (D) = 25 μm / 2 μm / 51 μm / 6 μm / 6 μm / 6 μm / 51 μm. The obtained multilayer structure is both hard and soft, and has excellent appearance characteristics, barrier properties (oxygen permeation rate, water vapor permeation rate), and mechanical properties, and can therefore be preferably used as a packaging material. In addition, since the ratio of the polyethylene-based material exceeds 0.9, the plastic can also be preferably reused as a so-called single-material packaging material.
[0236] Examples 2 to 8, 10 to 24, 26, 29 to 32, Comparative Examples 1 to 3, 6, 7
[0237] The type of EVOH, the type and content of polyvalent metal ions, the type and content of alkali metal ions, the type of adhesive resin (b), the type of polyethylene resin (c), the type of ethylene-α-olefin copolymer resin (d), and the type and content of higher fatty acid amide compound (e) were set as shown in Table 1 or Table 2, and the mold temperature, the distance from the mold to the cooling roll (air gap), and the cooling roll temperature when making the multilayer film were set as shown in Table 3 or Table 4. In the same manner as in Example 1, a multilayer film was produced and various measurements and evaluations were performed. It should be noted that, for Examples 4 and 5, a cooling treatment of blowing 10°C cold air on the surface of the thermoplastic resin layer (C) in the air gap was performed. The results are shown in Table 3 or Table 4.
[0238] Example 9
[0239] Dry EVOH pellets were prepared in the same manner as in Example 1 except that EVOH (a-4) (ethylene unit content of 44 mol%, saponification degree of 99.9 mol%, MFR (190°C, 2.16 kg load) when dried was 1.7 g / 10 min) was used instead of EVOH (a-1). A multilayer film was prepared in the same manner as in Example 1 except that 20 parts by mass of the obtained dry EVOH pellets were melt-kneaded with 80 parts by mass of the dry EVOH pellets obtained in Example 1 and magnesium stearate in such a manner that the content of magnesium ions in the obtained resin composition became 50 ppm. Various measurements and evaluations were performed. The results are shown in Table 3 or Table 4.
[0240] Embodiment 25
[0241] When manufacturing the stearamide masterbatch pellets, 10% by mass of spherical silica particles having an average particle size of 3.9 μm were added together with stearamide, and the same operation as in Example 1 was performed to prepare a multilayer film, and various measurements and evaluations were performed. The results are shown in Table 3 or Table 4. Compared with the multilayer film of Example 1, the multilayer film of this example has excellent smoothness of the film surface and good operability.
[0242] Example 27, Comparative Example 10
[0243] The film-making apparatus used in the manufacture of the multilayer film was changed to a 300 mm wide 6-layer co-extrusion multilayer casting film-making apparatus, and a multilayer film having a layer structure and layer thickness of (C) / (D) / (B2) / (A) / (B2) / (D)=19μm / 32μm / 6μm / 6μm / 6μm / 51μm was manufactured. The cooling roll temperature was set as described in Table 3 or Table 4. The multilayer film was manufactured by the same method as in Example 1, and various measurements and evaluations were performed. The results are shown in Table 3 or Table 4.
[0244] Embodiment 28
[0245] The film-making apparatus used in the manufacture of the multilayer film was changed to a 300 mm wide 6-layer co-extrusion multilayer casting film-making apparatus, and a multilayer film having a layer structure and layer thickness of (C) / (D) / (B2) / (A) / (B2) / (D)=34 μm / 17 μm / 6 μm / 6 μm / 6 μm / 51 μm was produced. The multilayer film was produced by the same method as in Example 1, and various measurements and evaluations were performed. The results are shown in Table 3 or Table 4.
[0246] Embodiment 33
[0247] A multilayer film having a layer structure and layer thickness of (C) / (B1) / (A) / (B2) / (D)=55.5 μm / 3 μm / 3 μm / 3 μm / 55.5 μm was prepared, and various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 3 or Table 4.
[0248] Comparative Examples 4 and 5
[0249] A multilayer film was prepared by the same method as in Example 1 except that a heat-sealed layer (D) was used instead of the thermoplastic resin layer (C) and the cooling roller temperature was changed as described in Table 3 or Table 4 to prepare a multilayer film having a layer thickness and layer structure of (D) / (B2) / (A) / (B2) / (D)=51μm / 6μm / 6μm / 6μm / 51μm. Various measurements and evaluations were performed. The results are shown in Table 3 or Table 4.
[0250] Comparative Examples 8 and 9
[0251] A multilayer film was prepared by the same method as in Example 1 except that a thermoplastic resin layer (C) was used instead of the heat-sealed layer (D) and the cooling roll temperature was changed as described in Table 3 or Table 4 to prepare a multilayer film having a layer thickness and layer structure of (C) / (B1) / (A) / (B1) / (C)=51μm / 6μm / 6μm / 6μm / 51μm. Various measurements and evaluations were performed. The results are shown in Table 3 or Table 4.
[0252] [Table 1]
[0253]
[0254] [Table 2]
[0255]
[0256] [Table 3]
[0257]
[0258] [Table 4]
[0259]
Claims
1. A multilayer film comprising: a barrier layer (A) comprising an ethylene-vinyl alcohol copolymer (a) having an ethylene unit content of 20 to 50 mol % and a saponification degree of 90 mol % or more as a main component, an adhesive layer (B) comprising an adhesive resin (b) as a main component, and a polyvinyl alcohol copolymer having a density of 0.941 to 0.980 g / cm 3 The thermoplastic resin layer (C) comprises a polyethylene resin (c) as a main component, and a layer having a density of 0.880 to 0.920 g / cm 3 The heat-sealing layer (D) has an ethylene-α-olefin copolymer resin (d) as a main component, A barrier layer (A) is provided between at least one set of thermoplastic resin layers (C) and the heat-sealing layer (D), does not have a layer containing a resin having a melting point of 200° C. or higher as a main component and a metal layer having a thickness of 1 μm or higher, When the temperature was increased from -50°C to 220°C at 10°C / min (first temperature increase) using a differential scanning calorimeter (DSC), then decreased to -50°C at 10°C / min, and further increased to 220°C at 10°C / min (second temperature increase), the ratio (H1 / H2) of the total heat of fusion at 0 to 150°C during the first temperature increase to the total heat of fusion at 0 to 150°C during the second temperature increase was 0.75 to 1.
01.
2. The multilayer film according to claim 1, wherein The first outermost layer has a thermoplastic resin layer (C), and the second outermost layer has a heat-sealing layer (D).
3. The multilayer film according to claim 1 or 2, wherein An adhesive layer (B1) is provided between the barrier layer (A) and the thermoplastic resin layer (C), and an adhesive resin (b1) as a main component of the adhesive layer (B1) has an acid value of 0.50 mgKOH / g or more and 2.50 mgKOH / g or less.
4. The multilayer film according to any one of claims 1 to 3, wherein The polyethylene resin (c) and the ethylene-α-olefin copolymer resin (d) each have an MFR (at 190° C. and under a load of 2.16 kg) measured in accordance with JIS K7210 (2014) of 0.5 to 2.0 g / 10 minutes.
5. The multilayer film according to any one of claims 1 to 4, wherein The ethylene-α-olefin copolymer resin (d) is a linear low-density polyethylene obtained by copolymerizing ethylene and an α-olefin having 6 or more carbon atoms.
6. The multilayer film according to any one of claims 1 to 5, wherein The heat-sealing layer (D) contains 100 to 7000 ppm of a higher fatty acid amide compound (e) having a melting point of 60 to 120°C.
7. The multilayer film according to any one of claims 1 to 6, wherein The heat-sealed layer (D) contains 500 to 5000 ppm of inorganic oxide particles (f) having an average particle size of 1 to 30 μm, and the inorganic oxide particles (f) are at least one selected from silicon oxide particles and metal oxide particles.
8. The multilayer film according to any one of claims 1 to 7, wherein The barrier layer (A) contains 10 to 200 ppm of at least one polyvalent metal ion (g) selected from the group consisting of magnesium ions, calcium ions, and zinc ions.
9. The multilayer film according to any one of claims 1 to 8, wherein The barrier layer (A) contains 10 to 400 ppm of alkali metal ions.
10. The multilayer film according to any one of claims 1 to 9, wherein The ethylene-vinyl alcohol copolymer (a) comprises EVOH (a1) and EVOH (a2), wherein the EVOH (a1) has an ethylene unit content of 22 mol% or more and less than 34 mol% and a saponification degree of 99 mol% or more, and the EVOH (a2) has an ethylene unit content of 34 mol% or more and less than 50 mol% and a saponification degree of 99 mol% or more.
11. The multilayer film according to any one of claims 1 to 10, wherein When the temperature was increased from -50°C to 220°C at 10°C / min (first temperature increase) using a differential scanning calorimeter (DSC), then decreased to -50°C at 10°C / min, and further increased to 220°C at 10°C / min (second temperature increase), the ratio (H1 / H2) of the total heat of fusion at 150-200°C during the first temperature increase to the total heat of fusion at 150-200°C during the second temperature increase was 0.90-1.
35.
12. The multilayer film according to any one of claims 1 to 11, wherein The total thickness of all layers is 200 μm or less, and the ratio of the thickness of the barrier layer (A) to the total thickness of all layers is 0.10 or less.
13. The multilayer film according to any one of claims 1 to 12, wherein The total thickness of all layers is 200 μm or less, and the ratio of the thickness of the thermoplastic resin layer (C) to the total thickness of all layers is 0.20 or more and 0.60 or less.
14. The multilayer film according to any one of claims 1 to 13, wherein the oxygen permeability of the multilayer film under the conditions of 20°C and 65% RH is 5 cc / (m 2 ·day·atm) or less.
15. The multilayer film according to any one of claims 1 to 14, wherein the water vapor transmission rate thereof at 40°C and 90% RH is 5 g / (m 2 · days) or less.
16. The multilayer film according to any one of claims 1 to 15, wherein After humidity conditioning at 23°C and 50% RH for 24 hours, the elongation at break when punctured at a speed of 50 mm / min with a needle having a tip diameter of 1 mm under the same conditions was 8.0 mm or more.
17. The multilayer film according to any one of claims 1 to 16, wherein After humidity conditioning at 23°C and 50% RH for 24 hours, the breaking strength when punctured at a speed of 50 mm / min with a needle having a tip diameter of 1 mm under the same conditions was 8.5 N or more.
18. The multilayer film according to any one of claims 1 to 17, which has a laminated structure in which a thermoplastic resin layer (C), an adhesive layer (B1), a barrier layer (A), an adhesive layer (B2) and a heat-sealing layer (D) are laminated in this order.
19. A multilayer structure comprising a laminate of the multilayer film according to any one of claims 1 to 18 and at least one resin layer (R) containing a thermoplastic resin (h) as a main component.
20. The multilayer structure according to claim 19, wherein The thermoplastic resin (h) contains polyethylene resin as a main component.
21. A packaging material comprising the multilayer film or multilayer structure according to any one of claims 1 to 20.
22. A recycling composition comprising a recycled product of the multilayer film or multilayer structure according to any one of claims 1 to 20.
23. A method for recovering a multilayer film or a multilayer structure, wherein: The multilayer film or multilayer structure according to any one of claims 1 to 20 is pulverized and then melt-molded.
Citation Information
Patent Citations
Multilayer structure and packaging material comprising same
WO2020071513A1
Resin composition including ethylene-vinyl alcohol copolymer, molded article, and multilayered structure
CN106661298A
Adhesive resin composition and layered body
CN113165363A
Multi-layered structure and method for manufacturing the same
JP2010208331A
Multilayer film, packing film and method for manufacturing the same, and packing material
TW201332767A